Coating Composition
Patent Information
- Application Number
- JP2022541625
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-01-14
- Filing Date
- 2021-01-13
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2041-01-13
Smart Images

Figure 0007633262000001 
Figure 0007633262000002 
Figure 0007633262000003
Abstract
Description
[Technical field]
[0001] The present invention relates generally to polyurethane-polysiloxane hybrid coating compositions (PUPSHCC), methods for preparing the coating compositions, and coated substrates, such as aircraft transparencies, incorporating the coating compositions. The present invention particularly relates to transparent coating compositions and coated aircraft transparencies that have improved erosion resistance, abrasion / scratch resistance, static dissipation capabilities, and environmental resistance. [Background technology]
[0002] Transparencies used in modern aircraft often require a protective coating or film disposed on the exterior surface to prevent damage to fragile underlying metallic or ceramic or polymeric conductive coatings such as gold, silver or indium tin oxide (ITO) or carbon nanotubes (CNTs). Such protective coatings and underlying conductive layers form a multi-layer electrostatic dissipative (ESD) coating system to provide the transparency with erosion resistance, abrasion / scratch resistance, static dissipative capabilities and environmental resistance. Organic polyurethane coatings and sol-gel based polysiloxane coatings are the two main families of such protective coatings used in these applications due to their outstanding light transmission and high optical clarity.
[0003] Polyester-based polyurethane coatings have elastomeric behavior, exhibiting excellent flexibility, toughness, tear, erosion and impact resistance, but lack abrasion / scratch resistance due to low hardness. On the other hand, sol-gel-based polysiloxane coatings have glassy behavior, exhibiting high hardness, abrasion and scratch resistance, but lack erosion and impact resistance due to brittleness. As a result of such differences in properties, the applications of polyurethane coatings and polysiloxane coatings are differentiated. Polyurethane coatings are selected as surface protective coatings in ESD coating systems for transparencies such as military canopies, pilot windshields and cockpit windows, where high erosion resistance is essential. Polysiloxane coatings are preferably used as surface protective coatings for cabin windows or side windows, where erosion resistance is less required. Thus, neither organic polyurethane coatings nor sol-gel-based polysiloxane coatings are considered to be completely satisfactory as universal surface protective coatings in ESD coating systems for transparencies used in modern aircraft. This is the current state of the art for surface protective coatings for aircraft transparencies. It can be readily appreciated that a need exists for a transparent coating composition that has the advantageous combination of good erosion and impact resistance, and good abrasion and scratch resistance, along with static dissipative ability and environmental resistance. Summary of the Invention [Means for solving the problem]
[0004] The present invention provides a two-component curable coating composition comprising: (A) a composition comprising an alkoxysilane-terminated polyester urethane prepolymer; and (B) a composition comprising a silanol-terminated polysiloxane prepolymer. In one embodiment, the two-component curable coating composition comprises: (A) Terminal groups of general formula (I):
[0005] [ka]
[0006] (In the formula, Y represents H; R1, where R1 represents hydrocarbyl, preferably alkyl or aryl; or Y is the group:
[0007] [ka] represents L is a hydrocarbylene group, preferably an alkylene or arylene group, preferably a C-C 10 a hydrocarbylene group, preferably methylene, ethylene or propylene, most preferably propyl; W1, W2, W3, W4, W5 and W6 may be the same or different and each independently represent -OR2, R2 may be the same or different at each occurrence, and each R2 is independently selected from an alkyl group, preferably the alkyl group has 1 to 10 carbon atoms, preferably the alkyl group has 1 to 8 carbon atoms, preferably methyl or ethyl, most preferably methyl). a composition comprising an alkoxysilane-terminated polyester urethane prepolymer comprising a prepolymer chain having the formula: and (B) A compound of general formula (II), (III) or (IV):
[0008] [ka] (In the formula, X1, X2, X3, X4, X5 and X6 each represent -OR3; R3 at each occurrence is the same or different and each independently selected from an alkyl group, preferably the alkyl group has 1 to 10 carbon atoms, 1 to 8 carbon atoms, 1 to 6 carbon atoms, and most preferably has 1 to 4 carbon atoms; m represents an integer of 1 to 6, preferably an integer of 1 to 3. A composition comprising a silanol-terminated polysiloxane prepolymer obtainable by the sol-gel process of an alkoxysilane selected from Includes.
[0009] The composition preferably further comprises one or more additives selected from a solvent, a urethane-forming catalyst, an antistatic agent, a stabilizer selected from one or more of a UV absorber, a light stabilizer, and a heat stabilizer, and a surface active agent selected from one or more of a flow or leveling agent and a surfactant. Preferably, the composition comprises at least two solvents, a urethane-forming catalyst, an antistatic agent, a UV absorber, a light stabilizer, a heat stabilizer, and a surfactant.
[0010] The alkoxysilane-terminated polyester urethane prepolymer (A) can be obtained by a process comprising the steps of: (i) reacting an aliphatic diisocyanate with a polyester diol to form an isocyanate-terminated polyester urethane prepolymer; and (ii) silanizing the isocyanate-terminated polyester urethane prepolymer with an amino-functional alkoxysilane.
[0011] The silanol-terminated polysiloxane prepolymer (B) can be obtained by the sol-gel process of an alkoxysilane, preferably an alkyl orthosilicate, selected from the group consisting of trialkoxysilanes, alkyl orthosilicates and bis(trialkyloxysilyl)alkanes.
[0012] The present invention further provides a polyurethane-polysiloxane hybrid coating composition (PUPSHCC) precursor obtainable by a process comprising a step of mixing or compounding composition (A) and composition (B). The polyurethane-polysiloxane hybrid coating composition (PUPSHCC) according to the present invention can be obtained by a process comprising a step of thermally curing the PUPSHCC precursor.
[0013] A further aspect of the present invention provides a method for preparing a two-component curable coating composition comprising: (1) preparing an alkoxysilane-terminated polyesterurethane prepolymer (A) by a process comprising: (i) reacting an aliphatic diisocyanate with a polyester diol to form an isocyanate-terminated polyesterurethane prepolymer; and (ii) silanating the isocyanate-terminated polyesterurethane prepolymer with an aminoalkoxysilane, as described herein; and (2) preparing a silanol-terminated polysiloxane prepolymer (B) by a sol-gel process of an alkoxysilane with at least one acid in the presence of a solvent comprising an alcohol and water, as described herein.
[0014] The present invention further provides the use of the two-component curable coating composition as a coating for substrates such as aircraft, particularly aircraft transparencies. The present invention further provides a substrate coated with the polyurethane-polysiloxane hybrid polymer coating composition of the present invention.
[0015] In a further aspect, a substrate coated with the polyurethane-polysiloxane hybrid polymer coating composition of the present invention can be prepared by a method comprising applying a polyurethane-polysiloxane hybrid coating composition precursor disclosed herein to a surface of a substrate, and thermally curing the coating composition precursor. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] The present invention utilizes the erosion and impact resistance of an organic polyurethane coating and the abrasion and scratch resistance of a sol-gel based polysiloxane coating by providing a unique modified hybrid composition that can be advantageously applied as a single coating onto the exterior surface of a substrate, such as an aircraft transparency, to provide the transparency with a surface protective layer that has the desired erosion and abrasion resistance, in addition to static dissipative and environmental performance.
[0017] The present invention provides a polyurethane-polysiloxane hybrid coating composition (PUPSHCC) that has advantageous properties of erosion resistance, impact resistance, and abrasion and scratch resistance, in addition to electrostatic dissipation and environmental resistance, and is therefore highly suitable as a surface coating for transparencies such as those used on modern aircraft, especially as a universal surface protective coating for ESD coating systems.
[0018] Unless otherwise indicated, the term "hydrocarbyl" as used throughout this specification refers to a univalent group formed by removing hydrogen from a hydrocarbon group. The term "hydrocarbyl" includes saturated or unsaturated hydrocarbyl groups, which may be aliphatic, cyclic or aromatic. The term "hydrocarbyl" refers to a univalent hydrocarbyl radical, such as an alkyl, alkenyl, cyclic alkyl or cyclic alkenyl, aryl, alkaryl or aralkyl group, which preferably contains 1 to 10 carbon atoms, particularly 1 to 8 carbon atoms, more particularly 1 to 6 carbon atoms, and most particularly 1 to 4 carbon atoms, and which may be linear, branched, cyclic, saturated and unsaturated species. Particularly preferred hydrocarbyl groups are methyl and ethyl.
[0019] The term "hydrocarbylene" as used herein, unless otherwise indicated, refers to a divalent group formed by removing two hydrogens from a hydrocarbon group. The term "hydrocarbylene" includes saturated or unsaturated hydrocarbylene groups, which may be aliphatic, cyclic or aromatic. The term "hydrocarbylene" refers to a divalent hydrocarbylene radical, preferably an alkylene or arylene group, such as an alkylene, alkenylene, cyclic alkylene or cyclic alkenylene, arylene, alkarylene or aralkylene group, which preferably contains 1 to 10 carbon atoms, particularly 1 to 8 carbon atoms, more particularly 1 to 6 carbon atoms, and most particularly 1 to 4 carbon atoms, and which may be linear, branched, cyclic, saturated and unsaturated species. Particularly preferred hydrocarbyl groups are methylene, ethylene and propylene, especially propylene.
[0020] The term "urethane grade solvent" refers to a solvent having 0.05 wt% water or less.
[0021] The present invention generally provides a two-component curable coating composition comprising (A) a composition comprising an alkoxysilane-terminated polyester urethane prepolymer, and (B) a composition comprising a silanol-terminated polysiloxane prepolymer obtainable by a sol-gel process of an alkoxysilane. Compositions (A) and (B), when compounded to form a polyurethane-polysiloxane hybrid coating composition (PUPSHCC) precursor, can be applied to a surface of a substrate and cured, optionally in the presence of a catalyst, to form a polyurethane-polysiloxane hybrid coating composition having advantageous properties such as one or more of high erosion resistance, high abrasion or scratch resistance, and impact resistance.
[0022] In one aspect, the present invention provides a method for producing a method for treating a cancer cell comprising: (A) Terminal groups of general formula (I):
[0023] [ka]
[0024] (In the formula, Y represents H; R1, where R1 represents hydrocarbyl (preferably R1 represents alkyl or aryl); or alternatively Y is the group:
[0025] [ka] represents L represents a hydrocarbylene group (preferably L is an alkylene or arylene group, preferably C-C 10 a hydrocarbylene group, preferably methylene, ethylene or propylene, most preferably propylene; W1, W2, W3, W4, W5 and W6 may be the same or different and each independently represent -OR2, R2 at each occurrence may be the same or different, each R2 is independently selected from an alkyl group, preferably said alkyl group having 1 to 10 carbon atoms, preferably said alkyl group having 1 to 8 carbon atoms, preferably methyl or ethyl, most preferably methyl). a composition comprising an alkoxysilane-terminated polyester urethane prepolymer comprising a prepolymer chain having the formula: and (B) A compound of general formula (II), (III) or (IV):
[0026] [ka] (In the formula, X1, X2, X3, X4, X5 and X6 each represent -OR3; R3 at each occurrence is the same or different and each occurrence is independently selected from an alkyl group (preferably, the alkyl group has 1 to 10 carbon atoms, 1 to 8 carbon atoms, 1 to 6 carbon atoms, and most preferably has 1 to 4 carbon atoms); m represents an integer of 1 to 6, preferably an integer of 1 to 3. A composition comprising a silanol-terminated polysiloxane prepolymer obtainable by the sol-gel process of an alkoxysilane selected from The present invention provides a two-component curable coating composition comprising:
[0027] In any aspect or embodiment of the invention, preferably, R1 at each occurrence is the same or different and each independently selected from a C1-C6 alkyl group, or a C1-C4 alkyl group. Preferably, R1 at each occurrence is the same and each represents a C1-C6 alkyl group or a C1-C4 alkyl group, preferably a methyl or ethyl group.
[0028] In any aspect or embodiment, the group Y is preferably H. Various additives may be added to the coating composition to provide additional advantageous properties. The additives may be added to the composition (A) and / or (B) either during the process for their preparation or after their preparation. Preferably, the compositions (A) and (B) include one or more of the following: one or more solvents; a urethane-forming catalyst; an antistatic agent; one or more stabilizers selected from one or more of a UV absorber, a light stabilizer, and a heat stabilizer; and one or more surface active agents selected from one or more of a flow or leveling agent and a surfactant.
[0029] In any embodiment of the present invention, composition (A) preferably further comprises an alkoxysilane terminated polyester urethane prepolymer, at least one solvent, flow or leveling agent, at least one stabilizer, a urethane-forming catalyst, and a surface additive. In a preferred embodiment, the solvent, flow or leveling agent, stabilizer, urethane-forming catalyst, and surface additive are added during the reaction to prepare the alkoxysilane terminated polyester urethane prepolymer of component (A).
[0030] In an optional embodiment of the present invention, the composition (B) further comprises a silanol-terminated polysiloxane prepolymer obtainable by sol-gel processing of an alkoxysilane selected from the compounds of general formula (II), (III) or (IV), at least one solvent and an antistatic additive. In a preferred embodiment, the solvent is present in the reaction mixture and the antistatic additive is added after the sol-gel process.
[0031] Preferably, in any embodiment of the present invention, composition (A) comprises an alkoxysilane terminated polyester urethane prepolymer, at least one solvent, a flow or leveling agent, at least one stabilizer, a urethane-forming catalyst and a surface additive, and composition (B) further comprises at least one solvent and an antistatic additive.
[0032] The various additives are discussed in more detail below.
[0033] solvent The composition of the present invention preferably includes a solvent as a composition medium and carrier. The solvent acts as a medium to improve flow properties and facilitate application of the composition as a coating to the surface of a substrate. A urethane grade solvent is preferably used.
[0034] In any aspect or embodiment of the present invention, the two-component curable composition preferably comprises at least one solvent, more preferably comprises two or more solvents. Preferably, composition (A) comprises an aprotic solvent and a protic solvent. Particularly suitable aprotic solvents may be selected from the group consisting of ethyl 3-ethoxypropionate (EEP), n-pentyl propionate (nPP), 2-butoxyethyl acetate (BEA), di-isobutyl ketone (DIBK) and methyl isobutyl ketone (MIBK) or combinations thereof. EEP is a particularly preferred aprotic solvent. Preferred protic solvents include hydroxyketones, preferably β-hydroxyketones, more preferably diacetone alcohol (DAA). The solvent may be present as a reaction solvent during the preparation of the alkoxysilane-terminated polyester urethane prepolymers and / or may be added after their preparation. For example, during the preparation of isocyanate-terminated polyester urethane prepolymers, the above-mentioned aprotic solvents are used to dilute the prepolymers and serve as the prepolymer medium.
[0035] In a preferred embodiment, composition (A) comprises an alkoxysilane-terminated polyester urethane prepolymer and a mixture of ethyl 3-ethoxypropionate and diacetone alcohol.
[0036] Preferably, composition (B) comprises one or more protic solvents, such as water or an alcohol, more preferably water and ethanol. Typically, a solvent is present in the sol-gel process for preparing the silanol-terminated polysiloxane prepolymer.
[0037] A protic solvent such as diacetone alcohol (DAA) is a good solvent for both the organic polyurethane portion and the sol-gel polysiloxane portion. DAA can be advantageously used as a co-solvent with EEP for PUPSHCC. A protic solvent such as DAA is mixed with an isocyanate-terminated polyester urethane prepolymer mixture as a medium for forming an alkoxysilane-terminated polyester urethane prepolymer by silanization of the isocyanate-terminated polyester urethane prepolymer with 3-aminopropyltrimethoxysilane (APTMS), an amino-functional alkoxysilane coupling agent.
[0038] Urethane forming catalyst A urethane-forming catalyst is preferably used in the preparation of the isocyanate-terminated polyester urethane prepolymer (the precursor to the alkoxysilane-terminated polyester urethane prepolymer of composition (A)) and in the thermal curing of the polyurethane-polysiloxane hybrid coating composition.
[0039] The urethane-forming catalyst promotes the formation of urethane bonds. Exemplary catalysts suitable for the present invention include organometallic compounds such as dibutyltin dilaurate and dibutyltin diacetate available from Sigma-Aldrich, and bismuth and zinc compounds available from Shepherd Chemical Company. The catalysts are typically used in the range of 0.1 ppm to 100 ppm, more typically 1 to 10 ppm, based on the total weight of solids in the composition.
[0040] Preferably, the catalyst is selected from the group consisting of dibutyltin dilaurate (DBTDL) and dibutyltin diacetate (DBTDA).
[0041] In some embodiments, a urethane-forming catalyst is present in the composition (A) of the two-component curable composition, for example as a catalyst used to prepare isocyanate-terminated polyester urethane prepolymer precursor to alkoxysilane-terminated polyester urethane prepolymer. The catalyst present in the preparation of isocyanate-terminated polyester urethane prepolymer can be carried over to the alkoxysilane-terminated polyester urethane prepolymer in sufficient amount to catalyze the thermal curing of the polyurethane-polysiloxane hybrid coating composition. In some embodiments, additional catalyst can be added before the final curing step (e.g., during the compounding step described below) to accelerate the curing process.
[0042] Antistatic Agent When the coating composition of the present invention is utilized as a protective coating for aircraft, it is desirable to provide static dissipative properties since the exterior surfaces of aircraft transparencies are typically subject to static charging, especially in high performance modern aircraft. This charging is caused by contact with ice crystals and other particles during flight, resulting in the transfer of charge to the surface via triboelectricity or friction. This phenomenon is referred to in the industry as precipitation charging or p-static charging.
[0043] P-static charging of the non-conductive (dielectric) outer surfaces of aircraft transparencies can cause several serious problems affecting aircraft performance, transparency life and crew safety. Discharges during flight can result in damage to the outer coating layers due to dielectric breakdown or can cause electronic interference to equipment. Such charge build-up can also result in electric shock hazards to flight and ground crew.
[0044] To prevent these problems caused by p-static charging, the outer layer of an aircraft transparency should be sufficiently conductive to allow charge to flow across the surface to the fuselage or through the thickness of the layer to a grounded conductive layer underneath. In such applications, antistatic agents are used in the two-component curable compositions of the present invention.
[0045] Thus, in any aspect or embodiment of the present invention, the two-component curable composition may further comprise an antistatic agent, preferably the antistatic agent is a hydrophilic or hydrophobic antistatic agent, more preferably the antistatic agent is a salt of (bis)trifluoromethane-sulfonimide, in particular the antistatic agent is lithium (bis)trifluoromethane-sulfonimide, tri-n-butylmethylammonium bis-(trifluoromethanesulfonyl)-imide or a quaternary alkylammonium salt of (bis)trifluoromethane-sulfonimide. These antistatic agents are available from 3M as Fluorad HQ 115, FC-4400 or FC-5000, respectively. The antistatic additive Fluorad HQ 115 is a hydrophilic ionic solid salt of lithium and fluorinated imide of formula Li+-N(SO2CF3)2. Antistatic additive FC-4400 is a hydrophobic ionic liquid salt of a quaternary ammonium and a fluorinated imide of the formula (n-C4H9)3(CH3)N+ -N(SO2CF3)2. Antistatic additive FC-5000 is a hydrophobic ionic liquid salt of a quaternary ammonium and a fluorinated imide with a single primary alcohol group on the quaternary ammonium of the formula R4N+ -N(SO2CF3)2. Antistatic additives are typically used in the range of 1 to 5 weight percent, more typically 2 to 3 weight percent, based on the total weight of solids in the composition. Most preferably, lithium (bis)trifluoromethanesulfonimide (Fluorad HQ 115) is used as the antistatic agent.
[0046] The two-component curable composition according to any aspect or embodiment of the present invention preferably comprises an antistatic agent in an amount of about 1 wt % to about 5 wt %, preferably about 2 wt % to about 3 wt %, based on the total weight of solids in the composition.
[0047] Stabilizers When used as a surface protective coating in ESD coating systems for transparencies used in modern aircraft, the use of the stabilizers in the compositions of the present invention can significantly improve the environmental resistance performance of the resulting PUPSHCC. Thus, in any aspect or embodiment of the present invention, the composition may further comprise one or more stabilizers, such as UV absorbers, light stabilizers, and heat stabilizers. These stabilizers, especially when used in combination (i.e., as a stabilizer package), provide effective stabilization against the adverse effects of light and weathering.
[0048] Preferably, the composition of the present invention comprises at least one UV absorber.Suitable UV absorbers are preferably selected from hydroxyphenyl-triazine, hydroxyphenyl-benzotriazole or hydroxyphenyl-benzophenone class UV absorbers.UV absorbers competitively absorb UV light that may be harmful to hybrid coating composition.
[0049] Representative UV absorbers suitable for the present invention include Tinuvin 400, Tinuvin 405, Tinuvin 460, Tinuvin 477 and Tinuvin 479 of the hydroxyphenyl-triazine class, and Tinuvin 928, Tinuvin 1130, Tinuvin 328, Tinuvin 99-2 and Tinuvin 384-2 of the hydroxyphenyl-benzotriazole class, available from BASF. The preferred UV absorber for the present invention is Tinuvin 479, which advantageously has an extremely high extinction coefficient in the UV-B and UV-A ranges. The high extinction coefficient allows the formulation of compositions with low UV absorber content.
[0050] Thus, in any aspect or embodiment of the invention, the composition preferably comprises: - mixture of 2-[4-[2-hydroxy-3-tridecyloxypropyl]oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine and 2-[4-[2-hydroxy-3-didecyloxypropyl]oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine (Tinuvin 400); - [2-hydroxy-4-[3-(2-ethylhexyl-1-oxy)-2-hydroxypropyloxy]phenyl]-4,6bis(2,4-dimethylphenyl)-1,3,5-triazine) (Tinuvin 405); - 2,4-bis(2-hydroxy-4-butoxyphenyl)-6-(2,4-dibutoxyphenyl)-1,3,5-triazine (Tinuvin 460); - 2-hydroxyphenyl-s-triazine containing 18-20% 2-methoxy-1-propyl-acetate (Tinuvin 477); - 6-Methylheptyl 2-[4-[4,6-bis(4-phenylphenyl)-1H-1,3,5-triazin-2-ylidene]-3-oxocyclohexa-1,5-dien-1-yl]oxypropanoate (Tinuvin 479); - 2-(2H-benzotriazol-2-yl)-6-(1-methyl-1-phenylethyl)-4-(1,1,3,3-tetramethylbutyl)phenol (Tinuvin 928); - a) a mixture of 50% b-[3-(2-H-benzotriazol-2-yl)-4-hydroxy-5-tert.butylphenyl]-propionic acid poly(ethylene glycol) 300-ester and b) 50% bis{b-[3-(2-H-benzotriazol-2-yl)-4-hydroxy-5-tert.butylphenyl]-propionic acid}-poly(ethylene glycol) 300-ester (Tinuvin 1130); - 2-(benzotriazol-2-yl)-4,6-bis(2-methylbutan-2-yl)phenol (Tinuvin 328); - 95% Benzenepropanoic acid, 3-(2H-benzotriazol-2-yl)-5-(1,1-dimethylethyl)-4-hydroxy-, C 7-9 - a mixture of branched and linear alkyl esters and 5% 2-propanol, 1-methoxy-, 2-acetate (Tinuvin 99-2); and - 95% mixture of benzenepropanoic acid, 3-(2H-benzotriazol-2-yl)-5-(1,1-dimethylethyl)-4-hydroxy-, C7-9-branched and linear alkyl esters, and 5% 1-methoxy-2-propyl acetate (Tinuvin 384-2) The composition comprises at least one UV absorber selected from the group consisting of:
[0051] Tinuvin 479 is a particularly preferred UV absorber.
[0052] Preferably, the composition of the present invention comprises at least one light stabilizer (light absorber). The light stabilizer is preferably a hindered amine light stabilizer (HALS). Such stabilizers are capable of trapping free radicals and act as radical scavengers in the autoxidation cycle, inhibiting the photooxidative degradation of polymeric materials. Representative light stabilizers suitable for the present invention include Tinuvin 123, Tinuvin 144, Tinuvin 152, Tinuvin 292 or Tinuvin 5100 available from BASF. The preferred light stabilizer for the present invention is Tinuvin 152, which has reactive primary hydroxyls that allow Tinuvin 152 to be cured into polyurethane-polysiloxane networks to improve compatibility and resistance to migration.
[0053] In any aspect or embodiment of the invention, the composition of the invention preferably comprises: - Decanedioic acid, bis(2,2,6,6-tetramethyl-1-(octyloxy)-4-piperidinyl) ester (Tinuvin 123); - Bis(1,2,2,6,6-pentamethyl-4-piperidinyl)-[[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]butylmalonate (Tinuvin 144); - 2,4-bis[N-butyl-N-(1-cyclohexyloxy-2,2,6,6-tetramethylpiperidin-4-yl)amino]-6-(2-hydroxyethylamine)-1,3,5-triazine (Tinuvin 152); - mixture of bis(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate (75-85%) and methyl 1,2,2,6,6-pentamethyl-4-piperidyl sebacate (15-25%) (Tinuvin 292); and - Liquid non-basic amino-ether (NOR) non-interacting hindered amine light stabilizer (Tinuvin 5100) The light absorbing agent is selected from the group consisting of:
[0054] In particular, the light absorber is selected from the group consisting of Tinuvin 123, Tinuvin 144, Tinuvin 152 and Tinuvin 292; or Tinuvin 123, Tinuvin 152 and Tinuvin 292.
[0055] According to any aspect or embodiment of the present invention, the composition disclosed herein preferably comprises at least one heat stabilizer.The heat stabilizer is typically a sterically hindered phenolic antioxidant that protects the composition against thermo-oxidative degradation.The representative heat stabilizer suitable for the present invention includes IRGANOX 1010, IRGANOX 1076, IRGANOX 1135 or IRGANOX 245 available from BASF.Low color, good compatibility, high resistance to extraction and low volatility are typical selection criteria of heat stabilizer for application in the present composition, and IRGANOX 1010 is one of the preferred ones.
[0056] Preferred heat stabilizers are selected from the group consisting of pentaerythritol tetrakis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate) (IRGANOX 1010); octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate (IRGANOX 1076); benzenepropanoic acid, 3,5-bis(1,1-dimethylethyl)-4-hydroxy-, C7-9-branched alkyl ester (IRGANOX 1135); and triethylene glycol bis(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate (IRGANOX 245), more preferably the heat stabilizer is pentaerythritol tetrakis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate) (IRGANOX 1010).
[0057] In any aspect or embodiment, the composition of the present invention preferably comprises a stabilizer combination (i.e., a stabilizer package) including a UV absorber, a light absorber, and a thermal stabilizer, and preferably the composition comprises a stabilizer combination of 6-methylheptyl 2-[4-[4,6-bis(4-phenylphenyl)-1H-1,3,5-triazin-2-ylidene]-3-oxocyclohexa-1,5-dien-1-yl]oxypropanoate (Tinuvin 479), 2,4-bis[N-butyl-N-(1-cyclohexyloxy-2,2,6,6-tetramethylpiperidin-4-yl)amino]-6-(2-hydroxyethylamine)-1,3,5-triazine (Tinuvin 152), and pentaerythritol tetrakis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate) (IRGANOX 1010). The Tinuvin 479 / Tinuvin 152 / IRGANOX 1010 combination stabilizer package provides particularly effective stabilization against the adverse effects of light and weathering. Stabilizer packages such as the Tinuvin 479 / Tinuvin 152 / IRGANOX 1010 combination can be added during the isocyanate-terminated polyester urethane prepolymer preparation.
[0058] In any aspect or embodiment of the invention, the composition of the invention preferably comprises one or more stabilizers in a total amount of about 0.5 wt % to about 4 wt %, preferably about 1 wt % to about 3 wt %, based on the total weight of solids in the two-component curable composition.
[0059] Surfactants Surface active agents or surfactants are preferred and may be used in the compositions of the present invention to control the wetting or spreading action of the coating, provide satisfactory flow and leveling properties to the coating surface, eliminate coating defects such as breaks and craters, and / or increase surface slip. The surface active agent may include a flow or leveling agent and / or a surfactant.
[0060] Flow / Leveling Agent According to any aspect or embodiment of the present invention, the composition may comprise a surfactant which is a flow or leveling agent, preferably the flow or leveling agent is a silicone based flow or leveling agent, in particular a modified siloxane silicone based flow or leveling agent, more preferably the flow or leveling agent is a surfactant available from Momentive Performance Materials, Inc. - Polyethylene glycol mono(3-(tetramethyl-1-(trimethylsiloxy)disiloxanyl)propyl)ether (Silwet L-77); - a mixture of siloxane polyalkylene oxide copolymer and octamethylcyclo-tetrasiloxane (Silwet L-7200); - Polyalkylene oxide modified polydimethylsiloxane organosilicon (Silwet L-7600); - an organosilicone surface tension reducer containing siloxane polyalkylene oxide copolymer and octamethylcyclotetrasiloxane (Silwet L-7604); - polyether silicones of polyalkylene oxide modified polydimethylsiloxanes (Silwet L-7605); and - Organosilicone surface tension reducer containing polyalkylene oxide modified polydimethylsiloxane (Silwet L-7657) and . The Silwet silicone surfactants are modified trisiloxanes with outstanding wetting, spreading and leveling properties. The powerful Silwet L-77, a very low molecular weight trisiloxane with polyether groups, is preferred for the present invention. Thus, the compositions of the present invention most preferably contain polyethylene glycol mono(3-(tetramethyl-1-(trimethylsiloxy)disiloxanyl)propyl)ether (Silwet L-77) as a flow or leveling agent.
[0061] Surfactants According to any aspect or embodiment of the present invention, the composition may include a surface active agent that is a surfactant. Exemplary surfactants suitable for the present invention include BYK Silicone Surface Additives, which are modified polydimethylsiloxanes to increase surface slip. More preferably, the surfactant is a polyether modified polydimethylsiloxane or a polyester modified polydimethylsiloxane. In particular, the surfactant may be: - Polyether modified polydimethylsiloxanes: BYK-300, BYK-306, BYK-313 and BYK-378, - Polyester modified polydimethylsiloxane: BYK-333 and BYK-370 Examples include those selected from the group consisting of:
[0062] Particularly preferred is reactive BYK-370, a polyester modified hydroxyl functional polydimethylsiloxane, which can be crosslinked through its primary OH groups into polyurethane-polysiloxane networks, permanently increasing surface slip.
[0063] In any aspect or embodiment of the invention, the composition of the invention comprises polyethylene glycol mono(3-(tetramethyl-1-(trimethylsiloxy)disiloxanyl)propyl)ether, a flow or leveling agent that is Silwet L-77, and a surfactant that is BYK-370. The use of Silwet L-77 and BYK-370 provides an excellent combination of spreading / flow / leveling and permanent surface slip.
[0064] Preferably, each surfactant is used in the range of 0.05 wt % to 1 wt %, more preferably in the range of 0.1 wt % to 0.5 wt %, based on the total weight of solids in the two-component curable composition.
[0065] In a preferred embodiment, composition (A) comprises at least one flow or leveling agent (preferably polyethylene glycol mono(3-(tetramethyl-1-(trimethylsiloxy)disiloxanyl)propyl)ether, Silwet L-77). The flow or leveling agent may be added to the reaction mixture for preparing the isocyanate-terminated polyester urethane prepolymer precursor to the alkoxysilane-terminated polyester urethane prepolymer. In another preferred embodiment, composition (A) further comprises at least one surfactant (preferably BYK-370), which may be added to the alkoxysilane-terminated polyester urethane prepolymer after the silane treatment reaction.
[0066] Alkoxysilane-terminated polyester urethane prepolymer Preferably, the alkoxysilane-terminated polyester urethane prepolymer in composition (A) is (i) reacting an aliphatic diisocyanate with a polyester diol to form an isocyanate-terminated polyester urethane prepolymer; and (ii) silanizing the isocyanate-terminated polyester urethane prepolymer with an amino-functional alkoxysilane to form an alkoxysilane-terminated polyester urethane prepolymer. The method can be obtained by a method comprising the steps of:
[0067] Steps (i) and (ii) are described in more detail below.
[0068] Isocyanate-terminated polyester urethane prepolymer The aliphatic diisocyanate in step (i) is preferably a monomeric aliphatic diisocyanate or a monomeric cycloaliphatic diisocyanate. Particularly suitable aliphatic diisocyanates include those selected from the group consisting of hexamethylene diisocyanate, methylene bis(4-cyclohexyl isocyanate) and isophorone diisocyanate. A particularly preferred aliphatic diisocyanate is methylene bis(4-cyclohexyl isocyanate), available as Desmodur W from Covestro.
[0069] The polyester diol is preferably a polycaprolactone-based polyester diol, preferably a linear polyester diol derived from a caprolactone monomer terminated with a primary hydroxyl group, more preferably the polyester diol can be obtained by catalytic ring-opening polymerization of the caprolactone monomer in the presence of a diol initiator. Preferably, the diol initiator is an alkylene diol or dialkylene glycol initiator. More specifically, the diol initiator is selected from the group consisting of 1,4-butanediol (BDO), diethylene glycol (DEG) and neopentyl glycol (NEO), most preferably diethylene glycol.
[0070] Preferably, the polyester diol has a molecular weight of about 300 g / mol to about 5000 g / mol, preferably about 380 g / mol to about 4500 g / mol, or about 600 g / mol to about 1000 g / mol, or in particular about 700 g / mol to about 900 g / mol, more particularly about 800 g / mol to about 850 g / mol.
[0071] Suitable polyester diols are preferably those obtainable by catalytic ring-opening polymerization of caprolactone in the presence of 1,4-butanediol, and preferably have a molecular weight of about 700 g / mol to about 900 g / mol. Representative polyester diols suitable for the preparation of the isocyanate-terminated polyester urethane prepolymers of the present invention include polycaprolactone-based Capa 2043, Capa 2054, Capa 2085, Capa 2100, Capa 2125, Capa 2205, Capa 2304 and Capa 2402 having an average molecular weight (g / mol) ranging from 400 to 4000, available from Perstorp Specialty Chemicals. The preferred polyester diol for the present invention is Capa 2085. Preferably, the molar amount of diisocyanate is in excess of the polyester diol. More preferably, the molar ratio of polyester diol to aliphatic diisocyanate in step (i) is from about 1:1.1 to about 1:5, from about 1:1.1 to about 1:4, from about 1:1.1 to about 1:2, from about 1:1.3 to about 1:1.7, or about 1:1.6.
[0072] Typically, in the reacting step (i), about 40 to 70 percent of the isocyanate functional groups of the aliphatic diisocyanate are converted to urethane bonds by the polyester diol, with unreacted isocyanate functional groups remaining at the ends of the urethane prepolymer.
[0073] A urethane-forming catalyst may be advantageously used in the preparation of the isocyanate-terminated polyester urethane prepolymer in step (i) and the subsequent thermal curing of the PUPSHCC. The catalyst promotes urethane bond formation. Representative catalysts suitable for the present invention are organometallic compounds and include dibutyltin dilaurate and dibutyltin diacetate available from Sigma-Aldrich, and bismuth and zinc compounds available from Shepherd Chemical Company. Preferably, the catalyst is dibutyltin dilaurate (DBTDL) or dibutyltin diacetate (DBTDA).
[0074] In a preferred embodiment, step (i) is carried out in the presence of a urethane-forming catalyst, preferably dibutyltin dilaurate or dibutyltin diacetate. The catalyst may be used in an amount ranging from 0.1 to 100 ppm, more typically from 1 to 10 ppm, based on the total weight of solids in the composition.
[0075] The urethane-forming catalyst is preferably carried over into the isocyanate-terminated polyester urethane prepolymer product of step (i) and into the alkoxysilane-terminated polyester urethane prepolymer component of composition (A) after silane treatment step (ii). Advantageously, the urethane-forming catalyst present in the resulting composition (A) can facilitate the curing step to prepare the final polyurethane-polysiloxane hybrid coating composition (PUPSHCC) without the need to add additional catalyst before curing. However, if necessary, an additional amount of urethane-forming catalyst may be added before the curing step.
[0076] When the above additives are used in the composition of the present invention to provide improved properties for certain applications of the coating composition (such as for aircraft transparency), some additives may be added to the reaction mixture for preparing the isocyanate-terminated polyester urethane prepolymer in step (i). Preferably, the reaction mixture in step (i) preferably contains one or more stabilizers as described above, preferably at least one additive selected from the group consisting of UV absorbers, light stabilizers and heat stabilizers, and flow / leveling agents as described above. More preferably, the reaction mixture in step (i) contains UV absorbers, light stabilizers, heat stabilizers and flow / leveling agents.
[0077] In a particularly preferred embodiment, the reaction mixture of step (i) comprises the following additives: a stabilizer package comprising a combination of Tinuvin 479 / Tinuvin 152 / IRGANOX 1010; and a flow / leveling agent which is polyethylene glycol mono(3-(tetramethyl-1-(trimethylsiloxy)disiloxanyl)propyl)ether (Silwet L-77).
[0078] Step (i) preferably includes heating the reaction mixture. The reaction mixture in step (i) is preferably heated to a temperature of about 50° C. to about 120° C., or about 60° C. to about 100° C., or about 70° C. to about 90° C. Preferably, the reaction time in step (i) is about 1 to about 4 hours, or preferably about 1 to about 3 hours. During the reaction, the reaction mixture is preferably continuously stirred. Preferably, the reaction is carried out in an inert atmosphere, preferably under nitrogen.
[0079] Following the reaction, the reaction mixture is preferably cooled. The resulting isocyanate-terminated polyester urethane prepolymer mixture may be diluted with a carrier solvent, and step (i) may further include adding an aprotic solvent to the isocyanate-terminated polyester urethane prepolymer to form a homogeneous mixture having a solids content of about 20 to about 80 wt%, preferably about 30 to about 70 wt%, more preferably about 40 to about 60 wt% (particularly about 50 to about 55 wt%). The aprotic solvent may be the same solvent used in the reaction mixture, and is preferably selected from the group consisting of ethyl 3-ethoxypropionate (EEP), n-pentylpropionate (nPP), 2-butoxyethyl acetate (BEA), di-isobutyl ketone (DIBK) and methyl isobutyl ketone (MIBK), and is more preferably 3-ethoxypropionate (EEP).
[0080] The product mixture comprising the isocyanate-terminated polyester urethane prepolymer from step (i) may be advantageously stored in a sealed container until required for the preparation of the alkoxysilane-terminated polyester urethane prepolymer. Typically, the product mixture from step (i) may have a pot life of up to about 6 months, or up to about 3 months.
[0081] In an illustrative example of the preparation of an isocyanate-terminated polyester urethane prepolymer in step (i), an aliphatic diisocyanate [such as methylene bis(4-cyclohexyl isocyanate) - Desmodur W] and a polyester diol (such as Capa 2085) may be heated to 82°C (180°F) in a stainless steel mixing pot equipped with a hot plate, agitator, nitrogen inlet and thermometer by heating with continuous agitation and nitrogen blanketing and maintaining at that temperature for 2 hours. The ratio of Desmodur W to polyester diol Capa 2085 is typically selected such that a range of 20 to 80 percent, more typically 40 to 70 percent, of the isocyanate functional groups of Desmodur W are converted to urethane linkages by the polyester diol and the unreacted isocyanate functional groups are at the ends of the urethane prepolymer. A urethane-forming catalyst such as dibutyltin dilaurate (DBTDL) or dibutyltin diacetate (DBTDA) is added to promote the reaction between Desmodur W and Capa 2085. A stabilizer package including UV absorbers, light stabilizers and heat stabilizers in the range of 0.5-4 weight percent for improved environmental performance, and optionally a surface active agent or surfactant for flow / leveling control and improved coating surface cosmetic properties can also be conveniently added during the isocyanate-terminated polyester urethane prepolymer preparation. The resulting isocyanate-terminated polyester urethane prepolymer can be diluted with ethyl 3-ethoxypropionate (EEP), a urethane-grade aprotic solvent, to a clear homogenous mixture having a solids content of approximately 50-60 weight percent.
[0082] Alkoxysilane-terminated polyester urethane prepolymer Step (ii) of the above process involves silanizing an isocyanate-terminated polyesterurethane prepolymer with an amino-functional alkoxysilane coupling agent to form an alkoxysilane-terminated polyesterurethane prepolymer component (A) which can be crosslinked with a separately prepared polysiloxane prepolymer of component (B) to form a PUPSHCC.
[0083] In any embodiment of the present invention, the amino-functional alkoxysilane in step (ii) is selected from the group consisting of aminoalkyltrialkoxysilanes, aminoaryltrialkoxysilanes, aminoalkyl(alkyl)(dialkoxyl)silanes, [bis(trialkoxylsilyl)-alkyl]amines, N-(aminoalkyl)-aminoalkyltrialkoxysilanes and N-alkyltrialkoxysilyl-N,N-dialkylamines; preferably, the amino-functional alkoxysilane is an aminoalkyltrialkoxysilane.
[0084] More preferably, the amino-functional alkoxysilane is selected from the group consisting of 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 4-aminobutyltrimethoxysilane, 4-aminobutyltriethoxy-silane, aminophenyltrimethoxysilane, aminophenyltriethoxysilane, 3-aminopropyl-methyldiethoxysilane, 3-aminopropylmethyldimethoxysilane, bis(trimethoxysilyl-propyl)amine, bis(triethoxysilylpropyl)amine and N-ethyl-3-trimethoxysilyl-2-methylpropaneamine.
[0085] 3-aminopropyltrimethoxysilane (APTMS) or 3-aminopropyltriethoxysilane (APTES) (available from Gelest or Sigma-Aldrich); especially 3-aminopropyltrimethoxysilane (APTMS) are particularly preferred amino-functional akoxysilanes for step (ii).
[0086] In a preferred embodiment, step (ii) comprises the addition of an amino-functional alkoxysilane to the isocyanate-terminated polyester urethane prepolymer. The silane treatment reaction is typically a rapid spontaneous reaction between the amino functionality of the amino-functional alkoxysilane and the isocyanate terminus of the isocyanate-terminated polyester urethane prepolymer.
[0087] Preferably, step (ii) is carried out in the presence of at least one aprotic solvent and a protic solvent, preferably as described above. The aprotic solvent may be the same solvent as used in the reaction mixture of step (i) as described above, with EEP being a particularly preferred aprotic solvent. A protic solvent may be added to the reaction mixture of step (ii). Preferred protic solvents include hydroxyketones, preferably β-hydroxyketones, more preferably diacetone alcohol (DAA). Step (ii) is most preferably carried out in a combination of aprotic and protic solvents, preferably a combination of EEP and DAA.
[0088] Step (ii) is preferably carried out at room temperature. The reaction is preferably carried out in an inert atmosphere, preferably under nitrogen.
[0089] The silanization reaction between the amino functional group of the amino-functional alkoxysilane coupling agent and the isocyanate terminus of the isocyanate-terminated polyester urethane prepolymer is typically a rapid spontaneous reaction accompanied by exothermic heat and urea bond formation. The silanization reaction is typically complete within 1 hour, and typically results in the alkoxysilane-terminated polyester urethane prepolymer as a clear homogeneous mixture in the aprotic / protic solvent (e.g., EEP / DAA).
[0090] When the above additives are used in the composition of the present invention to provide improved properties for certain applications of the coating composition (such as for aircraft transparencies), some additives may be added to the reaction mixture for preparing the alkoxysilane-terminated polyester urethane prepolymer of step (ii). In a preferred embodiment, at least one surface active agent, preferably a surfactant, more preferably a BYK silicone surface additive (modified polydimethylsiloxane), most preferably BYK-370, is added to the reaction product of step (ii).
[0091] Composition (A) comprising an alkoxysilane-terminated polyester urethane prepolymer typically has a pot life of about 8 to about 12 hours in a closed container at room temperature.
[0092] Silanol-terminated polysiloxane prepolymer (B) In any aspect or embodiment of the invention, the silanol-terminated polysiloxane prepolymer of composition (B) is an alkoxysilane of formula (II), (III) or (IV):
[0093] [ka] (In the formula, X1, X2, X3, X4, X5 and X6 each represent -OR3; R3 at each occurrence is the same or different and is independently selected from alkyl groups; m represents an integer from 1 to 6. It can be obtained by the sol-gel method.
[0094] Preferably, R3 is an alkyl group having 1 to 10 carbon atoms, more preferably R3 is an alkyl group having 1 to 8 carbon atoms, particularly 1 to 6 carbon atoms, and most preferably 1 to 4 carbon atoms.
[0095] In a preferred embodiment, m represents an integer of 1-3.
[0096] Preferably, in any embodiment of the present invention, each X1, X2, X3, X4, X5 and X6 represents an alkoxy group having 1 to 6 carbon atoms, more preferably 1 to 4 carbon atoms, more preferably methoxy or ethoxy.
[0097] Representative preferred alkoxysilanes suitable for forming the polysiloxane prepolymers of the present invention include tetraethylorthosilicate, tetramethylorthosilicate, methyltrimethoxysilane, methyltriethoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, 1,2-bis(triethoxysilyl)ethane, and 1,2-bis(trimethoxysilyl)ethane.
[0098] Fully hydrolyzed tetraethyl orthosilicate and tetramethyl orthosilicate can produce four silanol functional groups, which can participate in subsequent condensation with themselves or with alkoxysilane-terminated polyester urethane prepolymers for network formation. Fully hydrolyzed methyltrimethoxysilane, methyltriethoxysilane, ethyltrimethoxysilane and ethyltriethoxysilane can produce three silanol functional groups, which can participate in subsequent condensation with themselves or with alkoxysilane-terminated polyester urethane prepolymers for network formation. Fully hydrolyzed 1,2-bis(triethoxysilyl)ethane and 1,2-bis(trimethoxysilyl)ethane can produce six silanol functional groups, which can participate in subsequent condensation with themselves or with alkoxysilane-terminated polyester urethane prepolymers for network formation. Single alkoxysilanes or combinations of alkoxysilanes can be used to prepare polysiloxane prepolymers. In any embodiment of the present invention, the alkoxysilane is preferably tetramethyl orthosilicate or tetraethyl orthosilicate available from Gelest or Sigma-Aldrich, more preferably tetraethyl orthosilicate.
[0099] The sol-gel process is preferably carried out in an acidified aqueous organic solvent mixture. The water in the acidified aqueous organic solvent mixture hydrolyzes the alkoxysilanes to form polysiloxane prepolymers. The actual amount of water in the acidified aqueous organic solvent mixture can vary widely and can be readily determined empirically.
[0100] In a preferred embodiment, the silanol-terminated polysiloxane prepolymer of composition (B) can be obtained by a process comprising reacting an alkoxysilane, preferably an alkyltrioxysilane, an alkylorthosilicate or a bis(trialkyloxysilyl)alkane, more preferably an alkylorthosilicate (especially TEOS), with at least one acid in the presence of a solvent comprising alcohol and water.
[0101] The solvent component of the acidified aqueous organic solvent mixture for the formation of the silanol-terminated polysiloxane prepolymer of composition (B) of the present invention can be any solvent or combination of solvents that is compatible with the alkoxysilanes, their hydrolyzates, the formed polysiloxane prepolymer, and the alkoxysilane-terminated polyester urethane prepolymer that is compounded with the formed polysiloxane prepolymer.
[0102] Representative solvents suitable for forming the polysiloxane prepolymer of the present invention include alcohols (preferably methanol, ethanol, n-propanol, isopropanol, n-butanol); glycol ethers (preferably ethylene glycol dimethyl ether, propylene glycol dimethyl ether, propylene glycol methyl ether); diacetone alcohol, ketones (preferably methyl ethyl ketone, methyl isobutyl ketone, di-isobutyl ketone), and esters (preferably ethyl acetate, n-propyl acetate, n-butyl acetate, 2-butoxyethyl acetate, and ethyl 3-ethoxypropionate), and combinations thereof. Particularly preferred solvents for the aqueous organic solvent mixture are alcohols, more preferably the alcohols are selected from C1-C6 alcohols, especially C1-C3 alcohols, more preferably ethanol.
[0103] An organic acid or an inorganic acid, or a combination thereof, is used to acidify the aqueous organic solvent mixture and as a catalyst to promote the hydrolysis of the alkoxysilanes to form the silanol-terminated polysiloxane prepolymer of the present invention. Representative organic or inorganic acids suitable for forming the silanol-terminated polysiloxane prepolymer of the present invention include acetic acid, formic acid, malic acid, succinic acid, malonic acid, hydrochloric acid, nitric acid, sulfuric acid, phosphoric acid, and the like.
[0104] Preferably, the acid comprises a carboxylic acid and / or a mineral acid, preferably, the acid comprises a carboxylic acid and a mineral acid. The carboxylic acid is a C2-C6 alkyl carboxylic acid, preferably acetic acid.
[0105] Preferably, the mineral acid is selected from the group consisting of hydrochloric acid, sulfuric acid, nitric acid, hydrobromic acid, hydrofluoric acid and phosphoric acid, preferably the mineral acid is hydrochloric acid.
[0106] In a particularly preferred embodiment, the polysiloxane prepolymers may be conveniently prepared at room temperature by a sol-gel process of an alkoxysilane, preferably tetraethyl orthosilicate (TEOS), in an acidified aqueous organic solvent mixture with acetic acid or hydrochloric acid or a combination thereof.
[0107] The method preferably comprises adding an alkoxysilane to a mixture comprising at least one acid, water and an alcohol.
[0108] Preferably, the reaction mixture is maintained at a temperature of about 15° C. to about 30° C., about 18° C. to about 25° C., or about 20° C. to about 25° C., preferably for about 8 to about 120 hours, about 12 to about 96 hours, about 20 to about 60 hours, or about 30 to about 50 hours. The reaction mixture is preferably stirred continuously throughout the reaction period.
[0109] The acid is preferably present in an amount to maintain a pH in the range of about 1.5 to about 5, preferably about 1.8 to about 4.5, more preferably about 2 to about 4. The acid preferably comprises a combination of acetic acid and hydrochloric acid.
[0110] When the above additives are used in the composition of the present invention to provide improved properties for certain applications of the coating composition (such as for aircraft transparency), some additives may be added to the reaction mixture for preparing the silanol-terminated polysiloxane prepolymer. In a preferred embodiment, at least one antistatic agent (preferably, the antistatic agent is a hydrophilic or hydrophobic antistatic agent, more preferably, the antistatic agent is a salt of (bis)trifluoromethane-sulfonimide, in particular, the antistatic agent is lithium (bis)trifluoromethanesulfonimide, tri-n-butylmethylammonium bis-(trifluoromethanesulfonyl)imide, or a quaternary alkylammonium salt of (bis)trifluoromethanesulfonimide, most preferably, lithium (bis)trifluoromethanesulfonimide) is added to the reaction product.
[0111] Composition (B) prepared as described above can be stored in a sealed container at room temperature for up to about one week.
[0112] Polyurethane-Polysiloxane Hybrid Coating Composition (PUPSHCC) The PUPSHCC according to the present invention is prepared by combining the compositions (A) and (B) of the two-component curable composition as described in any aspect or embodiment herein and curing the composition. When the two-component curable composition is combined, it forms a curable composition (i.e., a polyurethane-polysiloxane hybrid coating composition precursor) that is thermosetting. The PUPSHCC precursor can be applied to a substrate and cured in situ on the substrate to form a coated substrate. The curing process results in crosslinking between the alkoxysilane-terminated polyester urethane component of composition (A) and the silanol-terminated polysiloxane prepolymer component of composition (B).
[0113] In a preferred embodiment, the PUPSHCC precursor is prepared by compounding the compositions (A) and (B) of the two-component curable composition as described in any of the aspects and embodiments described herein, optionally with a urethane-forming catalyst. The compounding can be carried out by continuous stirring (e.g., in a stainless steel pot). During the compounding step, the mixture is preferably degassed to obtain a homogeneous mixture.
[0114] Optionally, a urethane-forming catalyst may be added to the compounded mixture. The urethane-forming catalyst may be the same as the catalyst used to prepare the isocyanate-terminated polyester urethane prepolymer as described above. Preferably, the catalyst is selected from the group consisting of dibutyltin dilaurate (DBTDL) and dibutyltin diacetate (DBTDA). However, in some cases, component (A) may contain enough urethane-forming catalyst from the preparation of the isocyanate-terminated polyester urethane prepolymer, and additional catalyst may not be required in the compounded mixture.
[0115] Preferably, to facilitate application of the polyurethane-polysiloxane hybrid coating composition precursor to a substrate, the PUPSHCC precursor has a solids content of about 10 wt % to about 50 wt %, preferably about 20 wt % to about 40 wt %, or about 30 wt %.
[0116] To form a PUPSHCC, the PUPSHCC precursor prepared by the above method is optionally thermally cured after removal of at least a portion (preferably at least 80 wt%, at least 90 wt%, at least 95 wt%, or at least 98 wt%) of the solvent from the PUPSHCC precursor. The solvent may be removed by exposure to air for a sufficient length of time. Prior to thermal curing, the PUPSHCC precursor is preferably dried to a tack-free consistency.
[0117] In a preferred embodiment, heat curing involves heating the polyurethane-polysiloxane hybrid prepolymer to a temperature of from about 50°C to about 82°C, from about 60°C to about 82°C, or from about 70°C to about 82°C.
[0118] The present invention also relates to a method for preparing a two-component curable coating composition as defined in any aspect or embodiment herein, comprising the steps of: (1) preparing a composition (A) comprising an alkoxysilane-terminated polyester urethane prepolymer by a process comprising the steps of: (i) reacting an aliphatic diisocyanate with a polyester diol to form an isocyanate-terminated polyester urethane prepolymer; and (ii) silanizing the isocyanate-terminated polyester urethane prepolymer with an amino-alkoxysilane; (2) preparing a composition (B) comprising a silanol-terminated polysiloxane prepolymer by a sol-gel process of an alkoxysilane with at least one acid in the presence of a solvent comprising an alcohol and water; The present invention further provides a method comprising:
[0119] Components (A) and (B) of the two-component curable coating composition as defined in any aspect or embodiment can be compounded and applied to a substrate, and the resulting mixture can be thermally cured to provide a coated substrate.
[0120] The present invention further relates to the use of the compositions as described herein (i.e. the two-component curable compositions, the PUPSHCC and the PUPSHCC precursors) as coatings for substrates, preferably wherein the substrate is selected from the group consisting of aircraft, spacecraft, marine or vehicle parts, preferably aircraft parts, more preferably aircraft transparencies, most preferably aircraft windows and aircraft windscreens.
[0121] Following application of the PUPSHCC precursor to the surface to be coated, the coating is subjected to thermal curing (optionally followed by removal of the solvent) to provide a polyurethane-polysiloxane hybrid coating composition which is an alkyloxysilane terminated polyester urethane crosslinked with polysiloxane.
[0122] The present invention further provides a substrate, preferably an aircraft, spacecraft, marine or vehicle part, coated with a polyurethane-polysiloxane hybrid polymer coating. The substrate is preferably an aircraft part, preferably an aircraft transparency, more preferably an aircraft window or windscreen (windshield).
[0123] The present invention further provides a method for preparing a PUPSHCC coated substrate, the method comprising the steps of applying a polyurethane-polysiloxane hybrid coating composition precursor as defined in any embodiment herein to a surface of a substrate, removing at least a portion of the solvent from the polyurethane-polysiloxane hybrid coating composition precursor, preferably at least 80 wt%, at least 90 wt%, at least 95 wt%, or at least 98 wt% of the solvent, preferably by air drying, and thermally curing the coating composition precursor to provide a substrate coated with a polyurethane-polysiloxane hybrid coating composition.
[0124] The PUPSHCC precursor may be cured in situ on the substrate by heating, for example, in an oven to a temperature of about 50°C to about 82°C, about 60°C to about 82°C, or about 70°C to about 82°C.
[0125] In a preferred embodiment, the substrate is an aircraft transparency, preferably an aircraft window or windshield, and the surface of the substrate preferably comprises an electrically conductive layer, where the conductive layer is an indium tin oxide layer, and optionally a silicone binder layer on the conductive layer, onto which the polyurethane-polysiloxane hybrid coating composition precursor is applied.
[0126] In a preferred embodiment, the formulation of the PUPSHCC coated substrate comprises: 1) preparing a composition comprising an isocyanate-terminated polyester urethane prepolymer by reacting an aliphatic diisocyanate and a polyester diol, typically in the presence of a urethane-forming catalyst, and preferably in the presence of flow / leveling agents, UV absorbers, light and heat stabilizers, and at least one aprotic solvent; 2) converting the isocyanate-terminated polyester urethane prepolymer composition to an alkoxysilane-terminated polyester urethane prepolymer by silanization with an amino-functional alkoxysilane coupling agent to form a composition (A) comprising an alkoxysilane-terminated polyester urethane prepolymer; 3) preparing a composition (B) comprising a silanol-terminated polysiloxane prepolymer by a sol-gel process of an alkoxysilane in an acidified aqueous organic solvent mixture; 4) compounding compositions (A) and (B) to form a PUPSHCC precursor; 5) coating a substrate (preferably an aircraft transparency) with a PUPSHCC precursor and, optionally, removing at least a portion of the solvent from the PUPSHCC precursor; and 6) Heat curing step Includes.
[0127] In this method, an alkoxysilane-terminated polyester urethane prepolymer is crosslinked with a silanol-terminated polysiloxane prepolymer in a subsequent compounding / fluid coating / air drying / thermal curing step. For aircraft transparencies, the surface typically contains an electrically conductive indium tin oxide (ITO) or carbon nanotube (CNT) layer on the outer surface. A PUPSHCC precursor is applied to the surface to form a wet topcoat on the ITO or CNT layer. Subsequent drying and thermal curing steps convert the wet topcoat into a durable surface protective coating on the electrically conductive ITO or CNT layer, forming the desired ESD coating system on the outer surface of the aircraft transparencies to provide transparencies with improved erosion resistance, abrasion / scratch resistance, static dissipation capability, and environmental resistance.
[0128] A substrate obtainable by the above process, preferably an aircraft transparency, more preferably an aircraft window or aircraft windshield, is also provided by the present invention.
[0129] The present invention describes PUPSHCC, which can be modified with antistatic additives for electrical conductivity promotion, and a stabilizer package including UV absorbers, light stabilizers and heat stabilizers for improved environmental resistance, and the application of such coating compositions as a universal surface protective coating in an ESD coating system for transparencies used in modern aircraft to provide transparencies with improved erosion resistance, abrasion / scratch resistance, static dissipation capability and environmental resistance without increasing the complexity in the coating system and without compromising any performance properties compared to current state of the art materials.
[0130] The surface protective coating formed from the PUPSHCC of the present invention inherited the excellent rain erosion resistance from the comparative organic polyurethane and the excellent abrasion resistance from the comparative polysiloxane. The preferred embodiment as described in the following illustrative examples 1-7 showed that the surface protective coating formed from the optimized PUPSHCC had a Taber abrasion of percent haze increase ΔHz100 in the range of 2-3, which was even better than the typical results of the comparative polysiloxane while maintaining the excellent rain erosion resistance similar to that of the comparative polyurethane. The surface protective coating formed from the PUPSHCC of the present invention also showed the required electrostatic dissipation ability. Therefore, such a surface protective coating is considered to be suitable as a surface protective coating for the ESD coating system for transparency used in modern aircraft to provide transparency with improved erosion resistance, abrasion / scratch resistance, electrostatic dissipation ability and environmental resistance.
[0131] Other features and advantages of the present invention will become apparent from the following description of the preferred embodiments.
[0132] [Example] (1) Substrates for evaluating surface protective coatings Aircraft grade (per MIL-PRF-25690) stretched acrylic sheets with dimensions of 15 inches by 32 inches were cleaned using standard cleaning procedures, using cerium oxide, rinse water, tap water, DI water, heptane, and IPA in that order. For Examples 1-4 and 6-7 (i.e., ITO as conductive layer), the cleaned acrylic sheets were first primed with a polyurethane primer and air dried in a clean room for 2 hours. The primed acrylic sheets were then flow coated with a conductive indium tin oxide (ITO) layer, air dried for 1 hour, and heated in an air oven at 180°F for 1 hour. The ITO coated acrylic sheets were then used as substrates to evaluate transparent PUPSHCC. For Example 5 (CNT as conductive layer), the cleaned acrylic sheets were first flow coated with a carbon nanotube (CNT) conductive coating and air dried for 1 hour in a clean room. The CNT-coated acrylic sheet was then capped with a polyurethane layer, air dried for 1 hour, and heated in an air oven for 1 hour at 180° F. Transparent PUPSHCCs were then evaluated using either the ITO or CNT-coated acrylic sheets as substrates.
[0133] (2) Compounding and application of PUPSHCC The compounding of the sol-gel polysiloxane prepolymer and the alkoxysilane-terminated polyester urethane prepolymer was carried out in a stainless steel mixing pot with continuous stirring and degassing. The resulting PUPSHCC precursor is a transparent homogeneous coating mixture that can be conveniently flow-coated onto the outer surface of an aircraft transparency containing an electrically conductive ITO or CNT outer surface layer to form a wet topcoat on the ITO or CNT layer. Subsequent air drying and thermal curing steps convert the wet topcoat into a durable transparent surface protective coating on the electrically conductive ITO or CNT layer, forming the desired ESD coating system on the outer surface of the aircraft transparency to provide a transparency with improved erosion resistance, abrasion / scratch resistance, static dissipation capability and environmental resistance.
[0134] (3) Emphasis on performance relative to state of the art systems Table 1 highlights typical results for the key performance characteristics of rain erosion resistance, abrasion / scratch resistance, and static dissipation (see Measurements and Performance Testing section for test methods and procedures) for protective coatings formed from the PUPSHCC of the present invention and from comparative state of the art systems of organic polyurethane and sol-gel based polysiloxane.
[0135] [Table 1]
[0136] The performance highlights showed that the protective coating formed from the comparative organic polyurethane had excellent rain erosion resistance but poor abrasion / scratch resistance. On the other hand, the protective coating formed from the comparative polysiloxane had excellent abrasion / scratch resistance but had surface pitting on the test samples and failed rain erosion resistance. None of these prior art systems are considered to be entirely satisfactory as protective coatings for ESD coating systems for transparencies used in modern aircraft.
[0137] The PUPSHCC of the present invention can be best understood and illustrated by reference to the following examples. EXAMPLES
[0138] A) Preparation of Isocyanate-Terminated Polyester Urethane Prepolymer A stainless steel mixing pot equipped with a hot plate, agitator, nitrogen inlet and thermometer was charged with 691.0 g of polyester diol Capa 2085, 344.4 g of methylene bis(4-cyclohexyl isocyanate) Desmodur W, 4.2 g of flow / leveling agent Silwet L-77, 6.0 g of antioxidant heat stabilizer IRGANOX 1010, 12.0 g of UV absorber Tinuvin 479, 6.0 g of light stabilizer Tinuvin 152 and 0.4 g of aprotic solvent 0.5% dibutyltin dilaurate (DBTDL) diluted in ethyl 3-ethoxypropionate (EEP). The above ingredients were heated to 180°F and maintained at this temperature for 2 hours with continuous mixing and nitrogen blanketing. The resulting isocyanate terminated polyester urethane prepolymer was cooled to room temperature. Then, 950.0 g of an aprotic solvent, ethyl 3-ethoxypropionate (EEP), was added with stirring to dilute the prepolymer to a clear homogenous mixture having a solids content of approximately 53 weight percent. The isocyanate-terminated polyester urethane prepolymer mixture can be stored in a sealed container with a pot life of up to three months.
[0139] B) Preparation of trimethoxysilane-terminated polyester urethane prepolymer The isocyanate terminated polyester urethane prepolymer mixture prepared in step (A) was further diluted with 1000.0 g of diacetone alcohol (DAA) under continuous agitation and nitrogen blanketing. 150.0 g of an amino-functional alkoxysilane coupling agent, 3-aminopropyltrimethoxysilane (APTMS), was added to the urethane prepolymer mixture over a period of 10 minutes to silanize the isocyanate terminated polyester urethane prepolymer. The silanization between the amino functional groups of APTMS and the isocyanate termini of the polyester urethane prepolymer is a rapid spontaneous reaction accompanied by exotherm and urea bond formation. The silanization reaction was completed within 1 hour to produce a trimethoxysilane terminated polyester urethane prepolymer mixture in EEP / DAA. 6.0 g of surface additive BYK-370 was then added to the prepolymer mixture with agitation. The trimethoxysilane terminated polyester urethane prepolymer had a pot life of 8-12 hours at room temperature in a closed container.
[0140] C) Preparation of polysiloxane prepolymer A plastic container equipped with a lid, stir plate and magnetic stir bar was charged with 1021.0 g of ethanol, 112.0 g of DI water, 22.0 g of acetic acid and 2.0 g of hydrochloric acid. The above ingredients were stirred at room temperature for 5 minutes for the acidified aqueous alcoholic mixture. 320.0 g of tetraethyl orthosilicate (TEOS) was added to the acidified aqueous alcoholic mixture over 10 minutes with continuous stirring for the sol-gel polysiloxane prepolymer formation. The sol-gel process was maintained at room temperature for 2 days with gentle stirring. Then 36.0 g of hydrophilic antistatic additive Fluorad HQ 115 was added. The resulting polysiloxane prepolymer can be stored in a sealed container with a pot life of up to 1 week at room temperature.
[0141] D) Compounding and flow coating of PUPSHCC In a clean room, the trimethoxysilane terminated polyester urethane prepolymer prepared in step (B), the polysiloxane prepolymer prepared in step (C), and 2.0 g of 0.5% dibutyltin dilaurate (DBTDL) diluted in aprotic solvent ethyl 3-ethoxypropionate (EEP) were transferred to a stainless steel mixing pot equipped with an agitator and vacuum line for compounding. Compounding was carried out for 12 minutes with continuous stirring and degassing. The resulting PUPSHCC precursor was a clear homogenous mixture with a solids content of approximately 30 weight percent. The PUPSHCC precursor had a pot life of 1-2 hours.
[0142] The PUPSHCC precursor was then flow coated onto a previously prepared acrylic sheet measuring 15" x 32" with an electrically conductive ITO outer surface layer to form a wet topcoat on the ITO layer. After a 2 hour air dry and 24 hour 180°F oven cure step, the wet topcoat was converted into a transparent conductive surface protective coating on the electrically conductive ITO layer with a coating thickness of approximately 34 μm, light transmission of 91.1%, percent haze of 0.66, crosshatch adhesion of 100%, and Taber abrasion of percent haze increase ΔHz100=1.95. EXAMPLES
[0143] In this example, all coating materials and processing procedures, including compounding and flow coating procedures of isocyanate-terminated polyester urethane prepolymer, trimethoxysilane-terminated polyester urethane prepolymer, polysiloxane prepolymer, PUPSHCC, were the same as those of Example 1, except that the silicone binder was present on the ITO layer on the acrylic resin substrate. The resulting transparent conductive surface protective coating on the electrically conductive ITO layer had a coating thickness of approximately 29 μm, a light transmittance of 91.2%, a percent haze of 0.40, a cross-hatch adhesion of 100%, and a Taber abrasion of percent haze increase ΔHz100=2.63. EXAMPLES
[0144] A) Preparation of Isocyanate-Terminated Polyester Urethane Prepolymer An isocyanate-terminated polyester urethane prepolymer was prepared as in Example 1, step (A).
[0145] B) Preparation of trimethoxysilane-terminated polyester urethane prepolymer The isocyanate terminated polyester urethane prepolymer mixture prepared in step (A) was further diluted with 1400.0 g of diacetone alcohol (DAA) with continuous agitation and nitrogen blanketing. 150.0 g of an amino-functional alkoxysilane coupling agent, 3-aminopropyltrimethoxysilane (APTMS), was added to the urethane prepolymer mixture over a period of 10 minutes to silanize the isocyanate terminated polyester urethane prepolymer. The silanization between the amino functional groups of APTMS and the isocyanate termini of the polyester urethane prepolymer is a rapid spontaneous reaction accompanied by exotherm and urea bond formation. The silanization reaction was completed within 1 hour to produce a trimethoxysilane terminated polyester urethane prepolymer mixture in EEP / DAA. 6.0 g of surface additive BYK-370 was then added to the prepolymer mixture with agitation. The trimethoxysilane terminated polyester urethane prepolymer had a pot life of 8-12 hours at room temperature in a closed container.
[0146] C) Preparation of polysiloxane prepolymer A plastic container equipped with a lid, stir plate and magnetic stir bar was charged with 621.0 g of ethanol, 112.0 g of DI water, 22.0 g of acetic acid and 2.0 g of hydrochloric acid. The above ingredients were stirred at room temperature for 5 minutes for the acidified aqueous alcoholic mixture. 320.0 g of tetraethyl orthosilicate (TEOS) was added to the acidified aqueous alcoholic mixture over 10 minutes with continuous stirring for the sol-gel polysiloxane prepolymer formation. The sol-gel process was maintained at room temperature for 2 days with gentle stirring. Then 36.0 g of hydrophilic antistatic additive Fluorad HQ 115 was added. The resulting polysiloxane prepolymer can be stored in a sealed container with a pot life of up to 1 week at room temperature.
[0147] D) Compounding and flow coating of PUPSHCC In a clean room, the trimethoxysilane terminated polyester urethane prepolymer prepared in step (B), the polysiloxane prepolymer prepared in step (C), and 2.0 g of 0.5% dibutyltin dilaurate (DBTDL) diluted in aprotic solvent ethyl 3-ethoxypropionate (EEP) were transferred to a stainless steel mixing pot equipped with an agitator and vacuum line for compounding. Compounding was carried out for 12 minutes with continuous stirring and degassing. The resulting PUPSHCC precursor was a clear homogenous mixture with a solids content of approximately 30 weight percent. The PUPSHCC precursor had a pot life of 1-2 hours.
[0148] The PUPSHCC precursor was then flow coated onto a previously prepared acrylic sheet measuring 15" x 32" with an electrically conductive ITO outer surface layer to form a wet topcoat on the ITO layer. After a 2 hour air dry and 24 hour 180°F oven cure step, the wet topcoat was converted into a transparent conductive surface protective coating on the electrically conductive ITO layer with a coating thickness of approximately 31 μm, light transmission of 90.6%, percent haze of 0.54, crosshatch adhesion of 100%, and Taber abrasion of percent haze increase ΔHz100=2.71. EXAMPLES
[0149] In this example, all coating materials and processing procedures, including compounding and flow coating procedures of isocyanate-terminated polyester urethane prepolymer, trimethoxysilane-terminated polyester urethane prepolymer, polysiloxane prepolymer, PUPSHCC, were the same as those of Example 3, except that the silicone binder was present on the ITO layer on the acrylic resin substrate. The resulting transparent conductive surface protective coating on the electrically conductive ITO layer had a coating thickness of approximately 31 μm, a light transmittance of 90.8%, a percent haze of 0.52, a cross-hatch adhesion of 100%, and a Taber abrasion of percent haze increase ΔHz100=2.66. EXAMPLES
[0150] A) Preparation of Isocyanate-Terminated Polyester Urethane Prepolymer A stainless steel mixing pot equipped with a hot plate, agitator, nitrogen inlet and thermometer was charged with 691.0 g of polyester diol Capa 2085, 344.4 g of methylene bis(4-cyclohexyl isocyanate) Desmodur W, 4.2 g of flow / leveling agent Silwet L-77, 6.0 g of antioxidant heat stabilizer IRGANOX 1010, 12.0 g of UV absorber Tinuvin 479, 6.0 g of light stabilizer Tinuvin 152 and 0.4 g of 0.5% dibutyltin diacetate (DBTDA) diluted in aprotic solvent ethyl 3-ethoxypropionate (EEP). The above ingredients were heated to 180° F. and maintained at this temperature for 2 hours with continuous agitation and nitrogen blanketing. The resulting isocyanate terminated polyester urethane prepolymer was cooled to room temperature. Then, 950.0 g of an aprotic solvent, ethyl 3-ethoxypropionate (EEP), was added with stirring to dilute the prepolymer to a clear homogenous mixture having a solids content of approximately 53 weight percent. The isocyanate-terminated polyester urethane prepolymer mixture can be stored in a sealed container with a pot life of up to three months.
[0151] B) Preparation of trimethoxysilane-terminated polyester urethane prepolymer The isocyanate terminated polyester urethane prepolymer mixture prepared in step (A) was further diluted with 1400.0 g of diacetone alcohol (DAA) under continuous agitation and nitrogen blanketing. 150.0 g of an amino-functional alkoxysilane coupling agent 3-aminopropyltrimethoxysilane (APTMS) was added to the urethane prepolymer mixture over a period of 10 minutes to silanize the isocyanate terminated polyester urethane prepolymer. The silanization between the amino functional groups of APTMS and the isocyanate termini of the polyester urethane prepolymer is a rapid spontaneous reaction accompanied by exotherm and urea bond formation. The silanization reaction was completed within 1 hour to produce a trimethoxysilane terminated polyester urethane prepolymer mixture in EEP / DAA. 6.0 g of surface additive BYK-370 was then added to the prepolymer mixture with agitation. The trimethoxysilane terminated polyester urethane prepolymer had a pot life of 8-12 hours at room temperature in a closed container.
[0152] C) Preparation of polysiloxane prepolymer A plastic container equipped with a lid, stir plate and magnetic stir bar was charged with 621.0 g of ethanol, 112.0 g of DI water, 22.0 g of acetic acid and 2.0 g of hydrochloric acid. The above ingredients were stirred at room temperature for 5 minutes for the acidified aqueous alcoholic mixture. 320.0 g of tetraethyl orthosilicate (TEOS) was added to the acidified aqueous alcoholic mixture over 10 minutes with continuous stirring for the sol-gel polysiloxane prepolymer formation. The sol-gel process was maintained at room temperature for 2 days with gentle stirring. Then 36.0 g of hydrophilic antistatic additive Fluorad HQ 115 was added. The resulting polysiloxane prepolymer can be stored in a sealed container with a pot life of up to 1 week at room temperature.
[0153] D) Compounding and flow coating of PUPSHCC In a clean room, the trimethoxysilane terminated polyester urethane prepolymer prepared in step (B), the polysiloxane prepolymer prepared in step (C), and 2.0 g of 0.5% dibutyltin diacetate (DBTDA) diluted in aprotic solvent ethyl 3-ethoxypropionate (EEP) were transferred to a stainless steel mixing pot equipped with an agitator and vacuum line for compounding. Compounding was carried out for 12 minutes with continuous stirring and degassing. The resulting PUPSHCC precursor was a clear homogenous mixture with a solids content of approximately 30 weight percent. The PUPSHCC precursor had a pot life of 1-2 hours.
[0154] The PUPSHCC precursor was then flow coated onto a previously prepared acrylic sheet measuring 15 inches by 32 inches with an electrically conductive CNT outer surface layer to form a wet topcoat on the CNT layer. After a 2 hour air dry and 24 hour 180° F. oven cure step, the wet topcoat was converted into a transparent conductive protective surface coating on the electrically conductive CNT layer with a coating thickness of approximately 37 μm, light transmission of 90.9%, percent haze of 0.75, crosshatch adhesion of 100%, and Taber abrasion of percent haze increase ΔHz100=2.74. EXAMPLES
[0155] (Comparative Polyurethane Composition) An aliphatic polyester urethane composition of GKN code SS7008 was then flow coated onto the previously prepared acrylic sheet measuring 15 inches by 32 inches with an electrically conductive ITO outer surface layer to form a wet topcoat on the ITO layer. The coated acrylic sheet was then air dried and oven cured according to the process sheet. The resulting transparent surface protective coating on the electrically conductive ITO layer had a coating thickness of 74 μm, a light transmittance of 90.7%, a percent haze of 0.65, a cross-hatch adhesion of 100% and a Taber abrasion of percent haze increase ΔHz100=5.51. EXAMPLES
[0156] (Comparative Polysiloxane Composition) A polysiloxane composition obtained from SDC Technologies, Inc., GKN code SS6782, was then flow coated onto the previously prepared acrylic sheet measuring 15 inches by 32 inches with an electrically conductive ITO outer surface layer to form a wet topcoat on the ITO layer. The coated acrylic sheet was then air dried and oven cured according to the process sheet. The resulting transparent surface protective coating on the electrically conductive ITO layer had a coating thickness of 4.45 μm, a light transmittance of 92.6%, a percent haze of 0.50, a cross-hatch adhesion of 100%, and a Taber abrasion of percent haze increase ΔHz100=3.07.
[0157] Measurement and performance testing 1)Standard measurement The coating thickness of the protective coating on the electrically conductive ITO layer was measured with a QuintSonic Thickness Gauge. The light transmission and percent haze were measured with a Gardner haze-gard according to ASTM D-1003. Cross-hatch adhesion was measured according to ASTM D-3359.
[0158] 2) Taber abrasion as a measure of wear resistance The abrasion resistance of the coated acrylics was tested as Taber abrasion according to ASTM D-1044 by abrading approximately 4" x 4" samples of the coated acrylics using a Taber abrader equipped with a CS-10F abrasive wheel and 500g / arm. The percent haze increase of the abrasion pattern was measured over 100 cycles and expressed as ΔHz100, %.
[0159] 3)Static electricity dissipation test The static dissipation capability testing of the coated acrylics was performed at 75°F, 20°F, -20°F and -40°F using the method described in ASTM D-257. A coated acrylic sheet with dimensions 15 inches by 32 inches was first painted with a silver electrode over 1.0 square feet (12 inches by 12 inches) of the surface of the bottom area. The silver electrode painted acrylic sheet was then placed in a temperature controlled chamber and the surface electrode and the ITO conductive layer underneath were connected to a power source to record the relationship between current density and applied voltage at various temperatures. Applied voltages to set current densities of 80 μA / ft2 at 75°F, 40 μA / ft2 at 20°F, 20 μA / ft2 at -20°F, and 20 μA / ft2 at -40°F were measured in the range of 50V to 3,000V without dielectric breakdown of the surface protective coating formed from the PUPSHCC of the present invention. Such a protective coating having static dissipative capabilities is sufficiently conductive to allow surface charges to flow through the thickness of the protective coating to the underlying grounded ITO conductive layer, and therefore may be satisfactorily used as a protective coating in ESD coating systems for transparencies used in modern aircraft where static dissipative properties are required.
[0160] 4) Rain erosion test The coated acrylic test specimens were tested for rain erosion resistance. The coated acrylic was first cut to 1.00" x 1.00" x 0.25" dimensions, then the top end was machine stepped, filled with a gray elastomeric material, and the remaining sample surface of 3 / 32" thick x 3 / 16" wide was flushed and fitted into the holder of the tester. The rain erosion test parameters are an impact angle of 30 degrees, a rainfall of 1" per hour, and test speeds of 381 and 480 miles per hour. The average raindrop size is 2.0 mm. The test specimens were inspected for topcoat peeling or damage initially and after 30 minutes of exposure to rain. Less than 10% coating loss, peeling, or damage is considered a pass after testing.
[0161] 5) Accelerated QUV exposure Samples of the coated acrylic resin were tested for light transmission, percent haze, cross-hatch adhesion and overall appearance with accelerated QUV exposure for up to 5 weeks. The accelerated QUV equipment was operated with UVB-313 EL fluorescent lamps at cycles of 50°C / 7 hours UV exposure and 50°C / 5 hours condensation (UV off, high humidity). Test samples were removed from the QUV equipment once a week to check percent light transmission, percent haze, percent adhesion and overall appearance. Percent light transmission and percent haze are measured according to ASTM D-1003. Percent adhesion is measured according to ASTM D-3359. Surface protective coatings formed from PUPSHCC showed substantially no degradation of light transmission, percent haze, percent adhesion and overall appearance during QUV exposure, indicating excellent environmental resistance to the adverse effects of light and weathering.
[0162] Further aspects and embodiments of the invention are set out in the following numbered paragraphs.
[0163] 1. (A) A terminal group of general formula (I):
[0164] [ka]
[0165] (In the formula, Y represents H; R1, where R1 represents hydrocarbyl, preferably alkyl or aryl; or Y is the group:
[0166] [ka] L represents a hydrocarbylene group, preferably an alkylene or arylene group, preferably a C-C 10 a hydrocarbylene group, preferably methylene, ethylene or propylene, most preferably propylene; W1, W2, W3, W4, W5 and W6 may be the same or different and each independently represent -OR2, R2 at each occurrence may be the same or different, each R2 is independently selected from an alkyl group, preferably the alkyl group has 1 to 10 carbon atoms, preferably the alkyl group has 1 to 8 carbon atoms, preferably methyl or ethyl, most preferably methyl). a composition comprising an alkoxysilane-terminated polyester urethane prepolymer comprising a prepolymer chain having the formula: and (B) A compound of general formula (II), (III) or (IV):
[0167] [ka] (In the formula, X1, X2, X3, X4, X5 and X6 each represent -OR3; R3 at each occurrence is the same or different and each independently selected from an alkyl group, preferably an alkyl group having 1 to 10 carbon atoms, 1 to 8 carbon atoms, 1 to 6 carbon atoms, and most preferably 1 to 4 carbon atoms; m represents an integer of 1 to 6, preferably an integer of 1 to 3. A composition comprising a silanol-terminated polysiloxane prepolymer obtainable by the sol-gel process of an alkoxysilane selected from 1. A two-component curable coating composition comprising:
[0168] 2. The composition according to item 1, wherein the composition (A) and / or (B) comprises at least one or more of a solvent; a urethane-forming catalyst; an antistatic agent; a stabilizer selected from one or more of a UV absorber, a light stabilizer and a heat stabilizer; and a surface active agent selected from one or more of a flow or leveling agent and a surfactant, preferably, the composition (A) comprises at least one solvent, a flow or leveling agent, at least one stabilizer, a urethane-forming catalyst and a surface additive, and the composition (B) comprises at least one solvent and an antistatic additive.
[0169] 3. The composition according to item 1 or 2, wherein R1 at each occurrence is the same or different and each independently is selected from a C1-C6 alkyl or a C1-C4 alkyl group, preferably R1 is the same at each occurrence and each represents a C1-C6 alkyl or a C1-C4 alkyl group, preferably a methyl or ethyl group.
[0170] 4. The composition according to any of items 1 to 3, wherein Y is H.
[0171] 5. The composition according to any of items 1 to 4, comprising at least one solvent, preferably comprising two or more solvents, preferably the solvent comprises an aprotic solvent and a protic solvent, preferably the aprotic solvent is selected from the group consisting of ethyl 3-ethoxypropionate (EEP), n-pentyl propionate (nPP), 2-butoxyethyl acetate (BEA), di-isobutyl ketone (DIBK) and methyl isobutyl ketone (MIBK) or a combination thereof, and / or the protic solvent is a hydroxyketone, preferably a β-hydroxyketone, more preferably diacetone alcohol (DAA); preferably composition (A) comprises an alkoxysilane terminated polyester urethane prepolymer mixture in ethyl 3-ethoxypropionate and diacetone alcohol.
[0172] 6. The composition according to any of items 1 to 5, comprising a urethane-forming catalyst, preferably the urethane-forming catalyst is selected from the group consisting of dibutyltin dilaurate (DBTDL) and dibutyltin diacetate (DBTDA).
[0173] 7. The composition according to any of items 1 to 6, comprising a urethane-forming catalyst in an amount of about 0.1 ppm to about 100 ppm, preferably about 1 ppm to about 10 ppm, based on the total weight of solids in the composition.
[0174] 8. Preferably, the UV absorber is selected from a hydroxyphenyl-triazine, a hydroxyphenyl-benzotriazole or a hydroxyphenyl-benzophenone UV absorber, more preferably the UV absorber is - mixture of 2-[4-[2-hydroxy-3-tridecyloxypropyl]oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine and 2-[4-[2-hydroxy-3-didecyloxypropyl]oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine (Tinuvin 400); - [2-hydroxy-4-[3-(2-ethylhexyl-1-oxy)-2-hydroxypropyloxy]phenyl]-4,6bis(2,4-dimethylphenyl)-1,3,5-triazine) (Tinuvin 405); - 2,4-bis(2-hydroxy-4-butoxyphenyl)-6-(2,4-dibutoxyphenyl)-1,3,5-triazine (Tinuvin 460); - 2-hydroxyphenyl-s-triazine containing 18-20% 2-methoxy-1-propyl-acetate (Tinuvin 477); - 6-Methylheptyl 2-[4-[4,6-bis(4-phenylphenyl)-1H-1,3,5-triazin-2-ylidene]-3-oxocyclohexa-1,5-dien-1-yl]oxypropanoate (Tinuvin 479); - 2-(2H-benzotriazol-2-yl)-6-(1-methyl-1-phenylethyl)-4-(1,1,3,3-tetramethylbutyl)phenol (Tinuvin 928); - a) a mixture of 50% b-[3-(2-H-benzotriazol-2-yl)-4-hydroxy-5-tert.butylphenyl]-propionic acid poly(ethylene glycol) 300-ester and b) 50% bis{b-[3-(2-H-benzotriazol-2-yl)-4-hydroxy-5-tert.butylphenyl]-propionic acid}-poly(ethylene glycol) 300-ester (Tinuvin 1130); - 2-(benzotriazol-2-yl)-4,6-bis(2-methylbutan-2-yl)phenol (Tinuvin 328); - 95% Benzenepropanoic acid, 3-(2H-benzotriazol-2-yl)-5-(1,1-dimethylethyl)-4-hydroxy-, C 7-9 - a mixture of branched and linear alkyl esters and 5% 2-propanol, 1-methoxy-, 2-acetate (Tinuvin 99-2); and - 95% mixture of benzenepropanoic acid, 3-(2H-benzotriazol-2-yl)-5-(1,1-dimethylethyl)-4-hydroxy-, C7-9-branched and linear alkyl esters, and 5% 1-methoxy-2-propyl acetate (Tinuvin 384-2) 8. The composition according to any of items 1 to 7, selected from:
[0175] 9. A light absorber is included, preferably the light absorber is a hindered amine light stabilizer (HALS), more preferably - Decanedioic acid, bis(2,2,6,6-tetramethyl-1-(octyloxy)-4-piperidinyl) ester (Tinuvin 123); - Bis(1,2,2,6,6-pentamethyl-4-piperidinyl)-[[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]butylmalonate (Tinuvin 144); - 2,4-bis[N-butyl-N-(1-cyclohexyloxy-2,2,6,6-tetramethylpiperidin-4-yl)amino]-6-(2-hydroxyethylamine)-1,3,5-triazine (Tinuvin 152); - a mixture of bis(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate (75-85%) and methyl 1,2,2,6,6-pentamethyl-4-piperidyl sebacate (15-25%) (Tinuvin 292); or - Liquid nonbasic aminoether (NOR) non-interacting hindered amine light stabilizer (Tinuvin 5100) Selected from; Preferably, the composition according to any of items 1 to 8, wherein the light absorber is 2,4-bis[N-butyl-N-(1-cyclohexyloxy-2,2,6,6-tetramethylpiperidin-4-yl)amino]-6-(2-hydroxyethylamine)-1,3,5-triazine.
[0176] 10. The composition according to any of items 1 to 9, comprising a heat stabilizer, preferably the heat stabilizer is a sterically hindered phenol antioxidant, preferably selected from the group consisting of pentaerythritol tetrakis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate; octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate; benzenepropanoic acid, 3,5-bis(1,1-dimethylethyl)-4-hydroxy-, C7-9-branched alkyl ester; and triethylene glycol bis(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate, more preferably the heat stabilizer is pentaerythritol tetrakis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate).
[0177] 11. The composition according to any of items 1 to 10, comprising an antistatic agent, preferably the antistatic agent is a hydrophilic or hydrophobic antistatic agent, more preferably the antistatic agent is a salt of (bis)trifluoromethane-sulfonimide, in particular the antistatic agent is lithium (bis)trifluoromethanesulfonimide, tri-n-butylmethylammonium bis-(trifluoromethanesulfonyl)-imide, or a quaternary alkylammonium salt of (bis)trifluoromethane-sulfonimide, particularly preferably lithium (bis)trifluoromethanesulfonimide.
[0178] 12. The composition according to any of items 1 to 11, wherein the antistatic additive is present in the range of 1 to 5 weight percent, preferably in the range of 2 to 3 weight percent, based on the total weight of solids in the composition.
[0179] 13. The composition according to any of items 1 to 12, comprising a combination of stabilizers comprising a UV absorber, a light absorber and a heat stabilizer, preferably the composition comprises a combination of stabilizers of 6-methylheptyl 2-[4-[4,6-bis(4-phenylphenyl)-1H-1,3,5-triazin-2-ylidene]-3-oxocyclohexa-1,5-dien-1-yl]oxypropanoate (Tinuvin 479), 2,4-bis[N-butyl-N-(1-cyclohexyloxy-2,2,6,6-tetramethylpiperidin-4-yl)amino]-6-(2-hydroxyethylamine)-1,3,5-triazine (Tinuvin 152) and pentaerythritol tetrakis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate) (IRGANOX 1010).
[0180] 14. The composition according to any of items 1 to 13, comprising one or more stabilizers in a total amount of about 0.5 wt % to about 4 wt %, preferably about 1 wt % to about 3 wt %, based on the total weight of solids in the two-component curable composition.
[0181] 15. A flow or leveling agent is included, preferably the flow or leveling agent is a silicone based flow or leveling agent, in particular a modified siloxane silicone based flow or leveling agent, more preferably the flow or leveling agent is selected from the group consisting of polyethylene glycol mono(3-(tetramethyl-1-(trimethylsiloxy)disiloxanyl)propyl)ether (Silwet L-77); a mixture of siloxane polyalkylene oxide copolymer and octamethylcyclotetrasiloxane (Silwet L-7200); an organosilicone of polyalkylene oxide modified polydimethylsiloxane (Silwet L-7600); an organosilicone surface tension reducing agent comprising siloxane polyalkylene oxide copolymer and octamethylcyclotetrasiloxane (Silwet L-7604); a polyether silicone of polyalkylene oxide modified polydimethylsiloxane (Silwet L-7605); L-7605); and an organosilicone surface tension reducing agent comprising a polyalkylene oxide modified polydimethylsiloxane (Silwet L-7657); preferably, the flow or leveling agent is polyethylene glycol mono(3-(tetramethyl-1-(trimethylsiloxy)disiloxanyl)propyl)ether.
[0182] 16. The composition according to any of items 1 to 15, comprising a surfactant, preferably the surfactant is a silicone-based surface additive, preferably the surfactant is a polyether-modified polymethylsiloxane (in particular BYK-300, BYK-306, BYK-313 and BYK-378); or a polyester-modified polydimethylsiloxane (in particular BYK-333 and BYK-370).
[0183] 17. A composition according to any of items 1 to 16, comprising a flow or leveling agent which is polyethylene glycol mono(3-(tetramethyl-1-(trimethylsiloxy)disiloxanyl)propyl)ether (Silwet L-77), and a surfactant which is a polyester modified hydroxyl functional polydimethylsiloxane (BYK-370).
[0184] 18. The composition according to any of items 1 to 17, comprising one or more of a flow or leveling agent or a surfactant, each flow or leveling agent or surfactant being present in an amount of about 0.05 wt% to about 1 wt%, preferably about 0.1 wt% to about 0.5 wt%, based on the total weight of solids in the two-component composition.
[0185] 19. The alkoxysilane-terminated polyester urethane prepolymer in composition (A) is (i) reacting an aliphatic diisocyanate with a polyester diol to form an isocyanate-terminated polyester urethane prepolymer; and (ii) silanizing the isocyanate-terminated polyester urethane prepolymer with an amino-functional alkoxysilane to form an alkoxysilane-terminated polyester urethane prepolymer. 19. The composition according to any of items 1 to 18, which is obtainable by a process comprising the steps of:
[0186] 20. The composition according to item 19, wherein the aliphatic diisocyanate in step (i) is a monomeric aliphatic diisocyanate or a monomeric cycloaliphatic diisocyanate, preferably selected from hexamethylene diisocyanate, methylene bis(4-cyclohexyl isocyanate) and isophorone diisocyanate, more preferably methylene bis(4-cyclohexyl isocyanate).
[0187] 21. The composition according to item 19 or item 20, wherein the polyester diol is a polycaprolactone-based polyester diol, preferably a linear polyester diol derived from caprolactone monomers terminated with primary hydroxyl groups, more preferably the polyester diol is obtainable by catalytic ring-opening polymerization of caprolactone monomers in the presence of a diol initiator, preferably the diol initiator is an alkylene diol or dialkylene glycol initiator, most preferably the diol initiator is selected from the group consisting of 1,4-butanediol (BDO), diethylene glycol (DEG) and neopentyl glycol (NEO), in particular diethylene glycol.
[0188] 22. The composition according to any of items 19 to 21, wherein the polyester diol has a molecular weight of about 300 g / mol to about 5000 g / mol, preferably about 380 g / mol to about 4500 g / mol, or about 600 g / mol to about 1000 g / mol, or in particular about 700 g / mol to about 900 g / mol, in particular about 800 g / mol to about 850 g / mol.
[0189] 23. The composition according to any of items 18 to 22, wherein the polyester diol is obtainable by catalytic ring-opening polymerization of caprolactone in the presence of 1,4-butanediol initiator, and preferably has a molecular weight of about 700 g / mol to about 900 g / mol.
[0190] 24. The composition according to any of items 19 to 23, wherein the molar ratio of polyester diol to aliphatic diisocyanate in step (i) is from about 1:1.1 to about 1:5, from about 1:1.1 to about 1:4, from about 1:1.1 to about 1:2, from about 1:1.3 to about 1:1.7, or about 1:1.6.
[0191] 25. The composition according to any of items 19 to 24, wherein step (i) is carried out in the presence of a urethane-forming catalyst, preferably the catalyst is selected from the group consisting of dibutyltin dilaurate (DBTDL) and dibutyltin diacetate (DBTDA).
[0192] 26. The composition according to any of items 19 to 25, wherein the reaction mixture of step (i) preferably further comprises at least one additive selected from the group consisting of one or more stabilizers as defined in any of items 8 to 10, preferably UV absorbers, light stabilizers and heat stabilizers, and flow / leveling agents as defined in item 15.
[0193] 27. The composition according to any of items 19 to 26, wherein step (i) is carried out at a temperature of about 50°C to about 120°C, or about 60°C to about 100°C, or about 70°C to about 90°C.
[0194] 28. The composition according to any of items 19 to 27, wherein the reaction time in step (i) is from about 1 to about 4 hours, or preferably from about 1 to about 3 hours.
[0195] 29. The composition according to any of items 19 to 28, wherein step (i) further comprises adding an aprotic solvent to the isocyanate-terminated polyester urethane prepolymer to form a homogeneous mixture having a solids content of about 20 to about 80 wt %, preferably about 30 to about 70 wt %, more preferably about 40 to about 60 wt %.
[0196] 30. The composition according to item 29, wherein the aprotic solvent is selected from the group consisting of ethyl 3-ethoxypropionate (EEP), n-pentylpropionate (nPP), 2-butoxyethyl acetate (BEA), di-isobutyl ketone (DIBK) and methyl isobutyl ketone (MIBK), more preferably 3-ethoxypropionate (EEP).
[0197] 31. The amino-functional alkoxysilane of step (ii) is selected from the group consisting of aminoalkyltrialkoxysilanes, aminoaryltrialkoxysilanes, aminoalkyl(alkyl)(dialkoxy)silanes, [bis(trialkoxysilyl)-alkyl]amines, N-(aminoalkyl)-aminoalkyltrialkoxysilanes and N-alkyltrialkoxysilyl-N,N-dialkylamines, preferably said amino-functional alkoxysilanes are aminoalkyltrialkoxysilanes, preferably said amino-functional alkoxysilanes are 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 4-aminobutyltrimethoxysilane, 5-aminopropyltriethoxysilane, 6-aminopropyltriethoxysilane, 7-aminopropyltriethoxysilane, 8-aminopropyltriethoxysilane, 9-aminopropyltriethoxysilane, 10-aminopropyltriethoxysilane, 11-aminopropyltriethoxysilane, 12-aminopropyltriethoxysilane, 13-aminopropyltriethoxysilane, 14-aminopropyltriethoxysilane, 15-aminopropyltriethoxysilane, 16-aminopropyltriethoxysilane, 17-aminopropyltriethoxysilane, 18-aminopropyltriethoxysilane, 19-aminopropyltriethoxysilane, 20-aminopropyltriethoxysilane, 21-aminopropyltriethoxysilane, 22-aminopropyltriethoxysilane, 23-aminopropyltriethoxysilane, 24-aminopropyltriethoxysilane, 25-aminopropyltriethoxysilane, 26-aminopropyltriethoxysilane, 27-aminopropyltriethoxysilane, 28-aminopropyltriethoxysilane, 29-aminopropyltriethoxysilane, 30-aminopropyltriethoxysilane, 31-aminopropyltriethoxysilane, 32-aminopropyltriethoxysilane, 33-aminopropyltriethoxysil 31. The composition according to any of items 19 to 30, wherein the silane is selected from the group consisting of 4-aminobutyltriethoxy-silane, aminophenyltrimethoxysilane, aminophenyltriethoxysilane, 3-aminopropyl-methyldiethoxysilane, 3-aminopropylmethyldimethoxysilane, bis(trimethoxysilyl-propyl)amine, bis(triethoxysilylpropyl)amine, N-ethyl-3-trimethoxysilyl-2-methylpropanamine; more preferably, 3-aminopropyltrimethoxysilane (APTMS) and 3-aminopropyltriethoxysilane (APTES); most preferably, 3-aminopropyltrimethoxysilane (APTMS).
[0198] 32. The composition according to any of items 19 to 31, wherein step (ii) comprises adding an amino-functional alkoxysilane to an isocyanate-terminated polyester urethane prepolymer.
[0199] 33. A composition according to any of items 19 to 32, wherein step (ii) is carried out in the presence of at least one aprotic solvent, preferably as defined in item 30, and optionally further in the presence of a protic solvent in which the isocyanate-terminated polyester urethane prepolymer and the amino-functional alkoxysilane are soluble.
[0200] 34. The composition according to item 33, wherein the protic solvent is a hydroxyketone, more preferably a β-hydroxyketone, in particular diacetone alcohol (DAA).
[0201] 35. A composition according to any of items 19 to 34, wherein step (i) and / or step (ii), and preferably both, are carried out in an inert atmosphere, preferably under nitrogen.
[0202] 36. The composition according to any of items 19 to 35, wherein step (ii) further comprises adding at least one surfactant to the alkoxysilane-terminated polyester urethane prepolymer, preferably the surfactant being as defined in item 16.
[0203] 37. The composition according to any of items 1 to 36, wherein the silanol-terminated polysiloxane prepolymer (B) is obtainable by a sol-gel process of an alkyltrioxysilane, an alkylorthosilicate or a bis(trialkyloxysilyl)alkane, preferably an alkylorthosilicate, and preferably the silanol-terminated polysiloxane prepolymer (B) is obtainable by a sol-gel process of an alkoxysilane selected from the group consisting of tetraethylorthosilicate, tetramethylorthosilicate, methyltrimethoxysilane, methyltriethoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, 1,2-bis(triethoxysilyl)ethane and 1,2-bis(trimethoxysilyl)ethane, more preferably tetraethylorthosilicate.
[0204] 38. The composition according to any of items 1 to 37, wherein the silanol-terminated polysiloxane prepolymer in composition (B) is obtainable by a process comprising reacting an alkoxysilane, preferably an alkyltrioxysilane, an alkylorthosilicate or a bis(trialkyloxysilyl)alkane, more preferably an alkylorthosilicate, with at least one acid in the presence of a solvent comprising an alcohol and water.
[0205] 39. The composition according to item 38, wherein the method comprises adding an alkoxysilane to a mixture comprising at least one acid, water, and an alcohol.
[0206] 40. The composition according to item 38 or item 39, wherein the reaction mixture of step (a) is maintained at a temperature of about 15°C to about 30°C, about 18°C to about 25°C, or about 20°C to about 25°C, preferably for about 8 to about 120 hours, about 12 to about 96 hours, about 20 to about 60 hours, or about 30 to about 50 hours.
[0207] 41. The composition according to any of items 38 to 40, wherein the acid comprises a carboxylic acid and / or a mineral acid, preferably, the acid comprises a carboxylic acid and a mineral acid.
[0208] 42. The composition according to item 41, wherein the carboxylic acid is a C2-C6 alkyl carboxylic acid, preferably acetic acid.
[0209] 43. The composition according to item 41 or item 42, wherein the mineral acid is selected from the group consisting of hydrochloric acid, sulfuric acid, nitric acid, hydrobromic acid, hydrofluoric acid and phosphoric acid, preferably the mineral acid is hydrochloric acid.
[0210] 44. The composition according to any of items 38 to 43, wherein the acid is preferably present in an amount to maintain a pH in the range of about 1.5 to about 5, preferably about 1.8 to about 4.5, more preferably about 2 to about 4.
[0211] 45. The composition according to any of items 38 to 44, wherein the acid comprises acetic acid and hydrochloric acid.
[0212] 46. The composition according to any of items 38 to 45, wherein the alcohol is selected from C1-C6 alcohols, preferably C1-C3 alcohols, more preferably ethanol.
[0213] 47. The composition according to any of items 37 to 46, further comprising adding an antistatic agent to the silanol-terminated polysiloxane prepolymer, preferably wherein the antistatic agent is as defined in any of items 11 or 12.
[0214] 48. The composition according to any of items 19 to 47, wherein the molar ratio of the amino-functional alkoxysilane in step (ii) to the alkoxysilane of composition (B) is from about 1:4 to about 4:1, preferably from about 1:3 to about 3:1, and more preferably from about 1:2 to about 1:3.
[0215] 49. The composition according to any of items 1 to 48, which is heat curable, preferably in the presence of a catalyst, more preferably the catalyst is selected from the group consisting of dibutyltin dilaurate (DBTDL) and dibutyltin diacetate (DBTDA).
[0216] 50. A polyurethane-polysiloxane hybrid coating composition (PUPSHCC) precursor obtainable by a process comprising compounding composition (A) and composition (B) of a two-component curable composition as defined in any of items 1 to 49, optionally with a urethane-forming catalyst.
[0217] 51. The polyurethane-polysiloxane hybrid coating composition precursor according to item 50, wherein compounding comprises combining compositions (A) and (B), and optionally a urethane-forming catalyst, by agitation, preferably while degassing, to obtain a homogeneous mixture.
[0218] 52. The polyurethane-polysiloxane hybrid coating composition precursor according to item 51, wherein the compounding is carried out in the presence of a catalyst selected from the group consisting of dibutyltin dilaurate (DBTDL) and dibutyltin diacetate (DBTDA).
[0219] 53. A polyurethane-polysiloxane hybrid coating composition precursor according to any of items 50 to 52, having a solids content of about 10 wt% to about 50 wt%, preferably about 20 wt% to about 40 wt%, or about 30 wt%.
[0220] 54. A polyurethane-polysiloxane hybrid coating composition obtainable by a process comprising removing at least a portion of the solvent, preferably at least 80 wt%, at least 90 wt%, at least 95 wt%, or 98 wt% of the solvent, from the polyurethane-polysiloxane hybrid coating composition precursor of any of Items 50 to 53, preferably by air drying, and subjecting the PUPSHCC precursor to thermal curing.
[0221] 55. The polyurethane-polysiloxane hybrid coating composition according to item 54, wherein the thermal curing comprises heating the polyurethane-polysiloxane hybrid coating composition precursor to a temperature of from about 50°C to about 82°C, from about 60°C to about 82°C, or from about 70°C to about 82°C.
[0222] 56. A method for preparing a two-component curable coating composition as defined in items 1 to 49, comprising: (1) preparing a composition (A) comprising an alkoxysilane-terminated polyester urethane prepolymer by a process according to any one of items 20 to 36, comprising: (i) reacting an aliphatic diisocyanate with a polyester diol to form an isocyanate-terminated polyester urethane prepolymer; and (ii) silanizing the isocyanate-terminated polyester urethane prepolymer with an amino-alkoxysilane; and (2) A step of preparing a silanol-terminated polysiloxane prepolymer (B) by a sol-gel process of an alkoxysilane with at least one acid in the presence of a solvent containing alcohol and water according to any one of items 37 to 48. A method comprising:
[0223] 57. Use of a composition according to any of items 1 to 55 as a coating for a substrate, preferably wherein the substrate is selected from the group consisting of aircraft, spacecraft, marine and vehicle parts, preferably aircraft parts, more preferably aircraft transparencies, most preferably aircraft windows and aircraft windscreens.
[0224] 58. The use according to item 57, wherein the coating is subjected to thermal curing to result in a polyurethane-polysiloxane hybrid coating composition which is an alkyloxysilane terminated polyester urethane crosslinked with polysiloxane.
[0225] 59. A substrate, preferably an aircraft, spacecraft, marine vessel or vehicle part, comprising the polyurethane-polysiloxane hybrid polymer coating composition of item 54 or item 55.
[0226] 60. The substrate according to item 59, which is an aircraft part, preferably an aircraft transparency, more preferably an aircraft window or windscreen.
[0227] 61. A method for preparing a substrate according to item 59 or item 60, comprising the steps of applying a polyurethane-polysiloxane hybrid coating composition precursor as defined in any of items 50 to 53 to a surface of the substrate, removing at least a portion of the solvent from the polyurethane-polysiloxane hybrid coating composition precursor, preferably at least 80 wt%, at least 90 wt%, at least 95 wt%, or at least 98 wt% of the solvent, preferably by air drying, and thermally curing the coating composition precursor to provide a substrate coated with the polyurethane-polysiloxane hybrid coating composition.
[0228] 62. The method according to item 61, wherein the substrate is an aircraft transparency, preferably an aircraft window or windshield, and the surface of the substrate comprises an electrically conductive layer, preferably an indium tin oxide layer or a carbon nanotube layer, and optionally a silicone binder layer on the conductive layer, onto which the polyurethane-polysiloxane hybrid coating composition precursor is applied.
[0229] 63. The method according to either item 61 or item 62, wherein heat curing comprises heating to a temperature of about 50°C to about 82°C, about 60°C to about 82°C, or about 70°C to about 82°C.
[0230] 64. A substrate obtainable by the method according to any of items 61 to 63, wherein the substrate is preferably an aircraft transparency, more preferably an aircraft window or an aircraft windshield.
[0231] Although the present invention has been described in particular detail with reference to the above specific embodiments, the main purpose of which is to illustrate, many changes and modifications may be made by those skilled in the art without departing from the spirit and scope of the present invention as set forth in the following claims.
Claims
1. (A) A terminal group of general formula (I): 【Chemistry 1】 (In the formula, Y is H;R 1 represents R 1 represents hydrocarbyl; or Y represents the group: 【Chemistry 2】 represents L represents a hydrocarbylene group; W 1 , W 2 , W 3 , W 4 , W 5 and W 6 may be the same or different, and each independently represents -OR 2 represents R 2 may be the same or different for each occurrence, and each R 2 are independently selected from alkyl groups. a composition comprising an alkoxysilane terminated polyester urethane prepolymer comprising a prepolymer chain having the formula: and (B) A compound of general formula (II), (III) or (IV): 【Chemistry 3】 (In the formula, X 1 , X 2 , X 3 , X 4 , X 5 and X 6 are each -OR 3 represents; R 3 are the same or different at each occurrence and are each independently selected from alkyl groups; m represents an integer of 1 to 6. A composition comprising a silanol-terminated polysiloxane prepolymer obtainable by a sol-gel process of an alkoxysilane selected from a composition, wherein the sol-gel process comprises adding an alkoxysilane to a mixture comprising at least one acid and a solvent comprising water and an alcohol; 1. A two-component curable coating composition comprising:
2. R 1 represents alkyl or aryl. L represents an alkylene or arylene group, a C 1 -C 10 hydrocarbylene group, or a methylene, ethylene or propylene group; each R 2 is independently selected from an alkyl group having 1 to 10 carbon atoms or 1 to 8 carbon atoms, or is methyl or ethyl; each R 3 is independently selected from an alkyl group having 1 to 10 carbon atoms, 1 to 8 carbon atoms, 1 to 6 carbon atoms, or 1 to 4 carbon atoms; and / or The composition according to claim 1, wherein m represents an integer from 1 to 3.
3. 3. The composition of claim 1 or 2, wherein composition (A) and / or (B) comprises at least one or more of the following: a solvent; a urethane-forming catalyst; an antistatic agent; a stabilizer selected from one or more of a UV absorber, a light stabilizer, and a heat stabilizer; and a surface active agent selected from one or more of a flow or leveling agent and a surfactant.
4. A composition described in any of claims 1 to 3, wherein composition (A) comprises at least one solvent, a flow or leveling agent, at least one stabilizer, a urethane-forming catalyst, and a surface additive, and composition (B) comprises at least one solvent and an antistatic additive.
5. R 1 are the same or different at each occurrence, and each independently represent C 1 -C 6 Alkyl or C 1 -C 4 or selected from alkyl groups, R 1 are the same for each occurrence, and each 1 -C 6 Alkyl or C 1 -C 4 The composition according to any one of claims 1 to 4, which represents an alkyl group or a methyl or ethyl group.
6. The composition of any one of claims 1 to 5, wherein Y is H.
7. A composition according to any one of claims 1 to 6, comprising at least one solvent, or comprising two or more solvents.
8. The composition of claim 7, wherein the solvent comprises an aprotic solvent and a protic solvent.
9. The composition of claim 8, wherein the aprotic solvent is selected from the group consisting of ethyl 3-ethoxypropionate (EEP), n-pentylpropionate (nPP), 2-butoxyethyl acetate (BEA), di-isobutyl ketone (DIBK) and methyl isobutyl ketone (MIBK) or combinations thereof, and / or the protic solvent is a hydroxyketone, a beta-hydroxyketone, or diacetone alcohol (DAA).
10. The composition of claim 1, wherein composition (A) comprises a mixture of alkoxysilane-terminated polyester urethane prepolymers in ethyl 3-ethoxypropionate and diacetone alcohol.
11. The composition of any one of claims 1 to 10, further comprising a urethane-forming catalyst.
12. The composition of claim 11, wherein the urethane-forming catalyst is selected from the group consisting of dibutyltin dilaurate (DBTDL) and dibutyltin diacetate (DBTDA), and / or the urethane-forming catalyst is present in an amount of 0.1 ppm to 100 ppm, or 1 ppm to 10 ppm, based on the total weight of solids in the composition.
13. The composition of any one of claims 1 to 12, further comprising a UV absorber, a light absorber and a heat stabilizer.
14. The UV absorber comprises: mixture of 2-[4-[2-hydroxy-3-tridecyloxypropyl]oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine and 2-[4-[2-hydroxy-3-didecyloxypropyl]oxy]-2-hydroxyphenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine (Tinuvin 400); - [2-hydroxy-4-[3-(2-ethylhexyl-1-oxy)-2-hydroxypropyloxy]phenyl]-4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine) (Tinuvin 405); 2,4-bis(2-hydroxy-4-butoxyphenyl)-6-(2,4-dibutoxyphenyl)-1,3,5-triazine (Tinuvin 460); - 2-hydroxyphenyl-s-triazine containing 18-20% 2-methoxy-1-propyl-acetate (Tinuvin 477); 6-Methylheptyl 2-[4-[4,6-bis(4-phenylphenyl)-1H-1,3,5-triazin-2-ylidene]-3-oxocyclohexa-1,5-dien-1-yl]oxypropanoate (Tinuvin 479); 2-(2H-benzotriazol-2-yl)-6-(1-methyl-1-phenylethyl)-4-(1,1,3,3-tetramethylbutyl)phenol (Tinuvin 928); a) a mixture of 50% b-[3-(2-H-benzotriazol-2-yl)-4-hydroxy-5-tert. butylphenyl]-propionic acid poly(ethylene glycol) 300-ester and b) 50% bis{b-[3-(2-H-benzotriazol-2-yl)-4-hydroxy-5-tert. butylphenyl]-propionic acid}-poly(ethylene glycol) 300-ester) (Tinuvin 1130); 2-(benzotriazol-2-yl)-4,6-bis(2-methylbutan-2-yl)phenol (Tinuvin 328); - a mixture of 95% benzenepropanoic acid, 3-(2H-benzotriazol-2-yl)-5-(1,1-dimethylethyl)-4-hydroxy-, C 7-9 -branched and linear alkyl esters, and 5% 2-propanol, 1-methoxy-, 2-acetate (Tinuvin 99-2); and The composition according to claim 13, selected from the group consisting of 95% benzenepropanoic acid, 3-(2H-benzotriazol-2-yl)-5-(1,1-dimethylethyl)-4-hydroxy-, C7-9-branched and linear alkyl esters, and 5% 1-methoxy-2-propyl acetate (Tinuvin 384-2).
15. The composition of claim 13 or 14, wherein the light absorber is a hindered amine light stabilizer (HALS).
16. The hindered amine light stabilizer is - decanedioic acid, bis(2,2,6,6-tetramethyl-1-(octyloxy)-4-piperidinyl) ester (Tinuvin 123); - bis(1,2,2,6,6-pentamethyl-4-piperidinyl)-[[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]butyl malonate (Tinuvin 144); 2,4-bis[N-butyl-N-(1-cyclohexyloxy-2,2,6,6-tetramethylpiperidin-4-yl)amino]-6-(2-hydroxyethylamine)-1,3,5-triazine (Tinuvin 152); a mixture of bis(1,2,2,6,6-pentamethyl-4-piperidinyl)sebacate (75-85%) and methyl 1,2,2,6,6-pentamethyl-4-piperidylsebacate (15-25%) (Tinuvin 292); or The composition according to claim 15, wherein the light stabilizer is selected from the group consisting of liquid non-basic aminoether (NOR) non-interacting hindered amine light stabilizers (Tinuvin 5100).
17. A composition described in any one of claims 13 to 16, wherein the heat stabilizer is a sterically hindered phenolic antioxidant.
18. The composition according to claim 17, wherein the sterically hindered phenolic antioxidant is selected from the group consisting of pentaerythritol tetrakis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate); octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate; benzenepropanoic acid, 3,5-bis(1,1-dimethylethyl)-4-hydroxy-, C7-9-branched alkyl ester; and triethylene glycol bis(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate, or the heat stabilizer is pentaerythritol tetrakis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate).
19. The composition of any of claims 1 to 18, comprising a combination of stabilizers including a UV absorber, a light absorber and a thermal stabilizer.
20. The composition of claim 19, comprising a combination of the stabilizers 6-methylheptyl 2-[4-[4,6-bis(4-phenylphenyl)-1H-1,3,5-triazin-2-ylidene]-3-oxocyclohexa-1,5-dien-1-yl]oxypropanoate (Tinuvin 479), 2,4-bis[N-butyl-N-(1-cyclohexyloxy-2,2,6,6-tetramethylpiperidin-4-yl)amino]-6-(2-hydroxyethylamine)-1,3,5-triazine (Tinuvin 152) and pentaerythritol tetrakis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate) (IRGANOX 1010), and / or 20. The composition of claim 19, wherein the total amount of stabilizer is from 0.5 wt % to 4 wt %, or from 1 wt % to 3 wt %, based on the total weight of solids in the two-component curable composition.
21. The composition according to any one of claims 1 to 19, further comprising an antistatic agent.
22. The composition of claim 21, wherein the antistatic agent is a hydrophilic or hydrophobic antistatic agent.
23. The composition of claim 22, wherein the antistatic agent is a salt of (bis)trifluoromethanesulfonimide, or the antistatic agent is lithium (bis)trifluoromethanesulfonimide, tri-n-butylmethylammonium bis-(trifluoromethanesulfonyl)imide, or a quaternary alkylammonium salt of (bis)trifluoromethanesulfonimide.
24. A composition described in any of claims 21 to 23, wherein the antistatic additive is present in the range of 1 to 5 weight percent, or in the range of 2 to 3 weight percent, based on the total weight of solids in the composition.
25. The composition according to any one of claims 1 to 24, further comprising a flow or levelling agent and / or a surfactant.
26. The composition of claim 25, wherein the flow or leveling agent is a silicone-based flow or leveling agent.
27. The composition of claim 26, wherein the flow or leveling agent is a modified siloxane silicone-based flow or leveling agent.
28. The composition of claim 27, wherein the flow or leveling agent is selected from the group consisting of polyethylene glycol mono(3-(tetramethyl-1-(trimethylsiloxy)disiloxanyl)propyl)ether (Silwet L-77); a mixture of siloxane polyalkylene oxide copolymer and octamethylcyclotetrasiloxane (Silwet L-7200); an organosilicone of polyalkylene oxide modified polydimethylsiloxane (Silwet L-7600); an organosilicone surface tension reducing agent comprising a siloxane polyalkylene oxide copolymer and octamethylcyclotetrasiloxane (Silwet L-7604); a polyether silicone of polyalkylene oxide modified polydimethylsiloxane (Silwet L-7605); and an organosilicone surface tension reducing agent comprising a polyalkylene oxide modified polydimethylsiloxane (Silwet L-7657).
29. The composition according to claim 25, wherein the surfactant is a silicone-based surface additive.
30. The composition of claim 29, wherein the surfactant is a polyether-modified polymethylsiloxane or a polyester-modified polydimethylsiloxane.
31. The composition of any of claims 25 to 30, wherein the flow or leveling agent is polyethylene glycol mono(3-(tetramethyl-1-(trimethylsiloxy)disiloxanyl)propyl)ether (Silwet L-77) and the surfactant is a polyester modified hydroxyl functional polydimethylsiloxane (BYK-370).
32. The alkoxysilane-terminated polyester urethane prepolymer in the composition (A) is (i) reacting an aliphatic diisocyanate with a polyester diol to form an isocyanate-terminated polyester urethane prepolymer; and (ii) silanizing the isocyanate-terminated polyester urethane prepolymer with an amino-functional alkoxysilane to form an alkoxysilane-terminated polyester urethane prepolymer. The composition according to any one of claims 1 to 31, obtainable by a process comprising:
33. 33. The composition of claim 32, wherein the aliphatic diisocyanate in step (i) is a monomeric aliphatic diisocyanate or a monomeric cycloaliphatic diisocyanate, or is selected from hexamethylene diisocyanate, methylene bis(4-cyclohexyl isocyanate), and isophorone diisocyanate.
34. 34. The composition according to claim 32 or 33, wherein the polyester diol is a polycaprolactone-based polyester diol.
35. The composition of claim 34, wherein the polycaprolactone-based polyester diol is a linear polyester diol derived from caprolactone monomers terminated in primary hydroxyl groups.
36. The composition of claim 35, wherein the polyester diol is obtainable by catalytic ring-opening polymerization of caprolactone monomers in the presence of a diol initiator.
37. The composition of claim 36, wherein the diol initiator is an alkylene diol or dialkylene glycol initiator, or the diol initiator is selected from the group consisting of 1,4-butanediol (BDO), diethylene glycol (DEG), and neopentyl glycol (NEO).
38. The composition of any one of claims 32 to 37, wherein the polyester diol has a molecular weight of 300 g / mol to 5000 g / mol, 380 g / mol to 4500 g / mol, 600 g / mol to 1000 g / mol, 700 g / mol to 900 g / mol, or 800 g / mol to 850 g / mol.
39. 39. The composition of any of claims 32-38, wherein the molar ratio of polyester diol to aliphatic diisocyanate in step (i) is from 1:1.1 to 1:5, from 1:1.1 to 1:4, from 1:1.1 to 1:2, from 1:1.3 to 1:1.7, or from 1:1.
6.
40. The composition of any of claims 32 to 39, wherein step (i) is carried out in the presence of a urethane-forming catalyst.
41. The composition of claim 40, wherein the catalyst is selected from the group consisting of dibutyltin dilaurate (DBTDL) and dibutyltin diacetate (DBTDA), and / or the reaction mixture of step (i) further comprises one or more stabilizers selected from UV absorbers, light stabilizers and heat stabilizers as defined in any of claims 13 to 19, and at least one additive selected from the group consisting of flow / leveling agents as defined in any of claims 26 to 28 or 31.
42. 42. The composition of any of claims 32 to 41, wherein step (i) is carried out at a temperature of from 50°C to 120°C, or from 60°C to 100°C, or from 70°C to 90°C, and / or the reaction time of step (i) is from 1 to 4 hours, or from 1 to 3 hours.
43. 43. The composition of any of claims 32-42, wherein step (i) further comprises adding an aprotic solvent to the isocyanate-terminated polyester urethane prepolymer to form a homogeneous mixture having a solids content of 20-80 wt%, 30-70 wt%, or 40-60 wt%.
44. The composition of claim 43, wherein the aprotic solvent is selected from the group consisting of ethyl 3-ethoxypropionate (EEP), n-pentylpropionate (nPP), 2-butoxyethyl acetate (BEA), di-isobutyl ketone (DIBK) and methyl isobutyl ketone (MIBK), or the aprotic solvent is 3-ethoxypropionate (EEP).
45. 45. The composition of any of claims 32 to 44, wherein the amino-functional alkoxysilane in step (ii) is selected from the group consisting of aminoalkyltrialkoxysilanes, aminoaryltrialkoxysilanes, aminoalkyl(alkyl)(dialkoxy)silanes, [bis(trialkoxysilyl)-alkyl]amines, N-(aminoalkyl)-aminoalkyltrialkoxysilanes, and N-alkyltrialkoxysilyl-N,N-dialkylamines.
46. The composition of claim 45, wherein the amino-functional alkoxysilane is an aminoalkyltrialkoxysilane, or the amino-functional alkoxysilane is selected from 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 4-aminobutyltrimethoxysilane, 4-aminobutyltriethoxy-silane, aminophenyltrimethoxysilane, aminophenyltriethoxysilane, 3-aminopropyl-methyldiethoxysilane, 3-aminopropylmethyldimethoxysilane, bis(trimethoxysilyl-propyl)amine, bis(triethoxysilylpropyl)amine, N-ethyl-3-trimethoxysilyl-2-methylpropanamine, or the amino-functional alkoxysilane is selected from the group consisting of 3-aminopropyltrimethoxysilane (APTMS) and 3-aminopropyltriethoxysilane (APTES).
47. The composition of claims 32-46, wherein step (ii) comprises adding an amino-functional alkoxysilane to an isocyanate-terminated polyester urethane prepolymer; and / or step (ii) is carried out in the presence of at least one aprotic solvent.
48. The composition of claim 44, wherein at least one aprotic solvent is as defined in claim 44.
49. The composition of any one of claims 32 to 48, wherein step (ii) is carried out in the presence of a protic solvent in which the isocyanate-terminated polyester urethane prepolymer and the amino-functional alkoxysilane are soluble.
50. The composition of claim 49, wherein the protic solvent is a hydroxyketone, a β-hydroxyketone, or diacetone alcohol (DAA).
51. The composition of any of claims 32 to 50, wherein step (ii) further comprises adding at least one surfactant to the alkoxysilane terminated polyester urethane prepolymer.
52. The composition of claim 51, wherein the surfactant is as defined in any one of claims 29 to 31.
53. The composition according to any one of claims 1 to 52, wherein the silanol-terminated polysiloxane prepolymer (B) is obtainable by a sol-gel process of an alkyltrioxysilane, an alkylorthosilicate or a bis(trialkyloxysilyl)alkane.
54. The composition of claim 53, wherein the silanol-terminated polysiloxane prepolymer (B) is obtainable by a sol-gel process of an alkoxysilane selected from the group consisting of tetraethylorthosilicate, tetramethylorthosilicate, methyltrimethoxysilane, methyltriethoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, 1,2-bis(triethoxysilyl)ethane, and 1,2-bis(trimethoxysilyl)ethane, or the alkoxysilane is tetraethylorthosilicate.
55. The composition of claim 53 or 54, wherein the silanol-terminated polysiloxane prepolymer of composition (B) is obtainable by a process comprising reacting an alkoxysilane, an alkyltrioxysilane, an alkylorthosilicate or a bis(trialkyloxysilyl)alkane with at least one acid in the presence of a solvent comprising an alcohol and water.
56. The composition of any of claims 53 to 55, wherein the sol-gel reaction mixture is maintained at a temperature of 15°C to 30°C, 18°C to 25°C, or 20°C to 25°C, and / or for a period of 8 to 120 hours, 12 to 96 hours, 20 to 60 hours, or 30 to 50 hours.
57. The composition of any preceding claim, wherein the acid comprises a carboxylic acid and / or a mineral acid.
58. The composition of claim 57, wherein the carboxylic acid is a C2-C6 alkyl carboxylic acid, or the carboxylic acid is acetic acid, and / or the mineral acid is selected from the group consisting of hydrochloric acid, sulfuric acid, nitric acid, hydrobromic acid, hydrofluoric acid and phosphoric acid, or the mineral acid is hydrochloric acid.
59. 59. The composition of any of the preceding claims, wherein the acid is present in an amount to maintain a pH in the range of 1.5 to 5, 1.8 to 4.5, or 2 to 4, and / or the acid comprises acetic acid and hydrochloric acid.
60. The composition of any of claims 53 to 59, further comprising adding an antistatic agent to the silanol-terminated polysiloxane prepolymer.
61. The composition of claim 60, wherein the antistatic agent is as defined in any one of claims 20 to 24.
62. 62. The composition of any of claims 32-61, wherein the molar ratio of the amino-functional alkoxysilane in step (ii) to the alkoxysilane of composition (B) is from 1:4 to 4:1, from 1:3 to 3:1, or from 1:2 to 1:
3.
63. The composition of any of claims 1 to 62, which is thermosetting in the presence of a catalyst, or is thermosetting in the presence of a catalyst selected from the group consisting of dibutyltin dilaurate (DBTDL) and dibutyltin diacetate (DBTDA).
64. A polyurethane-polysiloxane hybrid coating composition (PUPSHCC) precursor obtainable by a process comprising compounding composition (A) and composition (B) of the two-component curable composition according to any one of claims 1 to 63.
65. The polyurethane-polysiloxane hybrid coating composition (PUPSHCC) precursor of claim 64, wherein the method comprises compounding composition (A) and composition (B) of the two-component curable composition with a urethane-forming catalyst.
66. The polyurethane-polysiloxane hybrid coating composition (PUPSHCC) precursor of claim 64 or 65, wherein compounding comprises combining compositions (A) and (B) by agitation and / or degassing to obtain a homogeneous mixture.
67. A polyurethane-polysiloxane hybrid coating composition (PUPSHCC) precursor described in any of claims 64 to 66, wherein the catalyst is selected from the group consisting of dibutyltin dilaurate (DBTDL) and dibutyltin diacetate (DBTDA).
68. A polyurethane-polysiloxane hybrid coating composition precursor as described in any one of claims 64 to 67, having a solids content of 10 wt % to 50 wt %, 20 wt % to 40 wt %, or 30 wt %.
69. A polyurethane-polysiloxane hybrid coating composition obtainable by a process comprising removing at least a portion of the solvent from the polyurethane-polysiloxane hybrid coating composition precursor according to any one of claims 64 to 68, and subjecting the PUPSHCC precursor to thermal curing.
70. The polyurethane-polysiloxane hybrid coating composition of claim 69, obtainable by a process comprising removing at least 80 wt %, at least 90 wt %, at least 95 wt %, or at least 98 wt % of the solvent from the polyurethane-polysiloxane hybrid coating composition precursor.
71. The polyurethane-polysiloxane hybrid coating composition of claim 69 or 70, wherein removing the solvent is by air drying and / or heat curing comprises heating the polyurethane-polysiloxane hybrid coating composition precursor to 50°C to 82°C, 60°C to 82°C, or 70°C to 82°C.
72. A process for preparing a two-component curable coating composition according to any one of claims 1 to 63, comprising the steps of: (1) preparing a composition (A) comprising an alkoxysilane-terminated polyester urethane prepolymer by a process as defined in any one of claims 33 to 52, comprising the steps of: (i) reacting an aliphatic diisocyanate with a polyester diol to form an isocyanate-terminated polyester urethane prepolymer; and (ii) silanizing the isocyanate-terminated polyester urethane prepolymer with an amino-alkoxysilane; and (2) preparing a silanol-terminated polysiloxane prepolymer (B) by a sol-gel process of alkoxysilanes with at least one acid in the presence of a solvent comprising alcohol and water according to the method as defined in any one of claims 53 to 62; The method comprising:
73. Use of a composition as defined according to any of claims 1 to 71 as a coating for a substrate.
74. The use of claim 73, wherein the substrate is selected from the group consisting of aircraft, aerospace aircraft, marine vessels and vehicle parts.
75. The use of claim 74, wherein the substrate is an aircraft transparency, an aircraft window or an aircraft windscreen.
76. The use of any one of claims 73 to 75, wherein the coating is subjected to thermal curing to provide a polyurethane-polysiloxane hybrid coating composition which is an alkyloxysilane terminated polyester urethane crosslinked with polysiloxane.
77. A substrate comprising a polyurethane-polysiloxane hybrid polymer coating composition as defined in any one of claims 69-71.
78. The substrate of claim 77, wherein the substrate is an aircraft part, an aircraft transparency, or an aircraft window or windscreen.
79. 79. A method for preparing a substrate according to claim 77 or 78, comprising the steps of applying a polyurethane-polysiloxane hybrid coating composition precursor according to claims 64-68 to a surface of a substrate, removing at least a portion of the solvent from the polyurethane-polysiloxane hybrid coating composition precursor, and thermally curing the coating composition precursor to provide a substrate coated with a polyurethane-polysiloxane hybrid coating composition.
80. The method of claim 79, wherein the substrate is an aircraft transparency, an aircraft window or a windshield, and a surface of the substrate comprises an electrically conductive layer.
81. The method of claim 80, wherein the electrically conductive layer is an indium tin oxide (ITO) layer or a carbon nanotube (CNT) layer and the polyurethane-polysiloxane hybrid coating composition precursor is applied thereon.
82. 82. The method of claim 81, wherein the substrate comprises a silicon binder layer on the electrically conductive layer.
83. At least 80 wt %, at least 90 wt %, at least 95 wt %, or at least 98 wt % of the solvent is removed from the polyurethane-polysiloxane hybrid coating composition precursor; and / or Air drying to remove the solvent, and / or thermally curing the coating composition precursor by heating to a temperature of from 50° C. to 82° C., from 60° C. to 82° C., or from 70° C. to 82° C.; A method according to any one of claims 79 to 82.
84. A substrate obtainable by the method according to any one of claims 79 to 83.
85. The substrate of claim 84, wherein the substrate is an aircraft transparency, an aircraft window or an aircraft windshield.
Citation Information
Patent Citations
Water-based anti-fouling self-cleaning polyurethane coating with high wear resistance and preparation method thereof
CN106675370A
Self cross-linkable silicone emulsion
JP2000119524A
Urethane resin composition, coating agent, coating agent for plastic substrate, and cured product obtained using these, and cured products obtained by using these, and methods for manufacturing the cured products
JP2012126819A
Cited By
Coating compositions
US12674072B2
Coating compositions
US20230066264A1